Electrode sheet and preparation method and application thereof
By blending phosphorus-based monomers into the electrode slurry of the lithium-ion battery and forming a phosphorus-based polymer material, the problem of thermal runaway in the lithium-ion battery under high temperature conditions is solved, and the effect of improving battery safety and electrochemical performance is achieved.
Patent Information
- Application Number
- CN202111163185.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-09-30
AI Technical Summary
Lithium-ion batteries are prone to thermal runaway under conditions such as overcharge, short circuit, needle puncture, and high temperatures. The existing phosphorus-based flame retardant only exerts the flame retardant effect at high temperatures and has a negative impact on battery performance.
By blending phosphorus-based monomers in the electrode slurry and forming an electrode sheet containing phosphorus-based polymer material by in-situ polymerization, a layer of phosphorus-based polymer material coated on the surface of the electrode active material particles is formed to improve the thermal stability and electrochemical stability of the electrode.
It effectively reduces the surface temperature of the battery cell, avoids dangers such as fire and explosion, improves the safety and cycle stability of the battery, and ensures the electrochemical performance of the battery.
Smart Images

Figure CN115911372B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrode sheet and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, low self-discharge rate and no memory effect, and have broad application prospects in the field of new energy electric vehicles. With the continuous development of science and technology, the requirements for the performance of lithium-ion batteries are getting higher and higher. With the continuous improvement of battery energy density, safety issues are becoming increasingly prominent.
[0003] Lithium-ion batteries face serious safety hazards mainly because the electrolyte they use is an organic liquid electrolyte, which has insufficient thermal and chemical stability, making the battery prone to thermal runaway under conditions such as overcharging, short circuit, puncture, and high temperature. At present, the electrolytes widely used in lithium-ion batteries are carbonate or ether electrolytes. In order to improve their safety, phosphorus-based compounds can be added to the electrolyte as flame retardants. Phosphorus-based flame retardants can produce phosphorus-based free radicals at high temperatures, cut off the chain reaction during the combustion of the electrolyte, and thus have a flame retardant effect to a certain extent. However, these phosphorus-based flame retardants usually can only exert their flame retardant effect at temperatures above 200°C; in addition, due to their properties such as high viscosity, high freezing point, chemical or electrochemical instability, they can only be used as additives and cannot fundamentally inhibit the temperature rise of the battery; and generally speaking, a large amount of phosphorus-based compounds need to be added to achieve good results. The addition of excessive phosphorus-based compounds often has a negative impact on other aspects of the battery performance, such as reducing energy density, charge and discharge rate, cycle stability, etc., thereby greatly reducing the overall performance of the battery.
[0004] Therefore, it is urgent to develop a comprehensive solution that can suppress thermal runaway of battery cells, improve the safety of electrodes and battery cells, and ensure that the battery cells have good electrochemical performance. Summary of the invention
[0005] In order to solve the above problems, the present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer with an electrode slurry, coating it on a current collector, and polymerizing it in situ to generate an electrode sheet containing a phosphorus-based polymer material. The in-situ mixing method in the electrode slurry is adopted to coat the surface of the electrode active material particles with a thin layer of polymer material containing phosphorus groups. Compared with general polymer electrolytes, the polymer layer has higher thermal stability and electrochemical stability, which can effectively reduce the surface activity of the electrode particles, reduce the direct contact between the active material particles and the electrolyte, inhibit the side reaction between the active material and the electrolyte, and improve the battery safety performance; in addition, the polymer layer can maintain a low interface impedance during the battery cycle, and at the same time, homogenize the ion flow, so that the electrode has good capacity performance and cycle stability, and ensures the electrochemical performance of the battery.
[0006] According to one aspect of the present application, an electrode sheet is provided, comprising a current collector and an electrode material covered on the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, and the electrode material further comprises a phosphorus-based polymer material; the mass proportion of the phosphorus-based polymer material in the electrode material is 0.08 to 20%; the monomer and the initiator are added during the slurry mixing process of the electrode material, and in-situ polymerization is performed to form the phosphorus-based polymer material; the monomer comprises a monomer A; the monomer A is at least one of the compounds shown in formula I,
[0007]
[0008] Among them, R is R 2 and R 3 Can be connected to -C=O or -O-; R 1 , R 2 , R 3 R is independently selected from any one of a chain or a ring with no, a substituent or a substituent; 4 and R 44 It is a chain saturated alkyl group which may be substituted.
[0009] Optionally, R 1 , R 3 R is independently selected from any one of a chain of 1 to 15 atoms with no, with or without substitution; 2 The moiety is selected from any one of a chain or a ring of 3 to 18 atoms which is free of substituents, has substituents or does not have substituents.
[0010] Optionally, the weight fractions of the components in the electrode material are: 80-98 parts of electrode active material, 0.2-10 parts of conductive agent, 0.2-10 parts of binder, and 0.1-20 parts of monomer.
[0011] Optionally, the monomer further comprises a monomer B; the monomer B is selected from at least one of the compounds shown in formula II,
[0012]
[0013] Among them, R 7 Selected from Any of the following;
[0014] A 1 , A 2 Indicates that the atoms in the ring / chain can be replaced by substituents;
[0015] Optionally, the substituent is halogen or OLi;
[0016] Preferably, the halogen is fluorine.
[0017] Optionally, the R6 includes at least one of an ester group, an amide group or a phenylamide group.
[0018] Optionally, R6 contains at least one ester group or amide group.
[0019] Optionally, the substituent includes H, a halogen atom, =O, =S, an alkyl group, a heteroalkyl group, an alkenyl group, a heteroalkenyl group, an alkynyl group, a heteroalkynyl group, a hydroxyl group, a carbonyl group, an aldehyde group, a carbonate group, a haloformyl group, a carboxyl group, an ester group, a peroxy group, an amine group (primary amine, secondary amine, tertiary amine, quaternary ammonium salt), an imino group (C=N), an imide (C(=O)NC(=O)), an azo group, a nitrate ester (RONO 2 ), at least one of a phosphate group, a thioether group, a disulfide group, a cyano group, a sulfonic acid group, a sulfonyl group, an amide group, a nitro group, a pyridyl group, an acyloxy group, a phenyl group, a benzyl group, a benzyloxy group, a phenoxy group, an acetyl group, a benzoyl group, and a benzyloxycarbonyl group.
[0020] Optionally, the molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
[0021] According to another aspect of the present application, a method for preparing an electrode sheet as described above is provided, wherein the preparation method is in-situ polymerization.
[0022] Optionally, the preparation method comprises:
[0023] (1) taking the above-mentioned portions of electrode active material, conductive agent, binder, monomer, and initiator, and mixing them uniformly to prepare a uniformly mixed slurry;
[0024] (2) coating the uniformly mixed slurry on a current collector and polymerizing the mixture in situ to obtain the electrode sheet;
[0025] The temperature of the in-situ polymerization is 45-130° C., and the time of the in-situ polymerization is 0.1-60 min. The mass fraction of the initiator in the mixed slurry is 0.001%-2%. The coating speed is 0.5m / min-75m / min.
[0026] According to another aspect of the present application, a battery is provided, comprising at least one of the electrode sheets as described above and the electrode sheets obtained by any of the preparation methods as described above.
[0027] Technical effects:
[0028] (1) The present application provides a new type of electrode sheet system, that is, a monomer containing a phosphorus group is mixed into an electrode slurry, and an electrode sheet containing a phosphorus-based polymer material is obtained through in-situ polymerization. The phosphorus-based polymer material is formed by copolymerization of one or two monomers, that is, the phosphorus-based polymer contains a variety of different functional groups and heteroatoms. Through the interaction between different functional groups and heteroatoms, it can protect the active materials on the surface of the electrode sheet, reduce the surface activity of the active particles of the electrode sheet, and inhibit the temperature rise of the battery, thereby significantly reducing the surface temperature of the battery cell and avoiding the dangers of fire and explosion of the battery; it achieves the condition of taking into account high energy density and greatly improving the safety of the battery. It also has a strong anti-extrusion ability and can maintain the structure and performance of the battery itself, thereby improving the safety of the battery, improving the cycle stability of the battery, and extending the service life of the battery.
[0029] (2) The present application generates a layer of phosphorus-based polymer material in situ on the surface of the electrode active material particles by in-situ mixing of phosphorus-based monomers in the electrode slurry. Compared with the coating of the entire positive electrode material, the coating is refined to each electrode particle, which has a better coating effect, more effectively reduces the surface activity of the electrode particles, reduces the direct contact between the active material particles and the electrolyte, inhibits the side reactions between the active material and the electrolyte, and improves the battery safety performance; in addition, the polymer layer can maintain a low interfacial impedance during the battery cycle, and at the same time homogenizes the ion flow, so that the electrode has good capacity and cycle stability, and ensures the electrochemical performance of the battery. In addition, the in-situ curing preparation process is simple, safe and environmentally friendly, greatly reduces the use and emission of organic solvents, is compatible with existing liquid battery processes, and is easy to quickly promote industrialization. Compared with the non-in-situ curing process, the in-situ curing process will make the coating more uniform, which can better improve the battery safety and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a battery cycle comparison chart of battery 1-1, battery 1-2 and blank battery 1 of the present application; the horizontal axis is the number of cycles, in units of times; the vertical axis is the capacity retention rate, in units of %.
[0031] Figure 2 It is a graph showing the battery puncture test results of battery 1-1(a), battery 1-2(b), battery 9-2(c), battery 1-4(d), battery 1-11(e) and blank battery 1(f) of the present application. DETAILED DESCRIPTION
[0032] The specific implementation of the present application is described below in conjunction with the accompanying drawings.
[0033] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields. At the same time, in order to better understand the present invention, the definitions and explanations of the relevant terms are provided below.
[0034] In the embodiments of the present application, the polymerization degrees p and n of the polymer units in the polymer material structure can be calculated using the number average molecular weight method.
[0035] The number-average molecular weight is the most commonly used method for calculating the degree of polymerization. Polymer materials are composed of polymer units with the same chemical composition but different degrees of polymerization. The number-average molecular weight (Mn) can be obtained by averaging the number of molecules. Number-average molecular weight = sum of molecular weights of each component * number of moles of component / total number of moles. The calculation formula of number-average molecular weight is prior art and will not be described in detail here.
[0036] In this example, the H NMR spectrum 1 In H NMR, s represents a singlet, d represents a doublet, t represents a triplet, q represents a quartet, m represents a multiplet (multiplet greater than four, such as a quintet, sextet, etc.), dd represents a doublet, and dt represents a doublet; the number before the bracket represents the chemical shift, and the number before H in the bracket represents the number of H, such as 2.22 (s, 2H), which means that there are two Hs with a chemical shift of 2.22, and the peak is a singlet. Other situations can be deduced by analogy and will not be repeated.
[0037] In this example, MS (ESI) m / z …… (MH) + Represents mass spectrum.
[0038] In the embodiments of the present application, 0.1C / 0.1C means charging at a rate of 0.1C and discharging at a rate of 0.1C; 0.5C / 0.5C means charging at a rate of 0.5C and discharging at a rate of 0.5C.
[0039] In the present application, monomers for preparing phosphorus-based polymer materials are mixed in positive and negative electrode slurries, and through an in-situ curing process, pole pieces containing polymer materials are formed to further prepare the battery.
[0040] Wherein, the battery assembly also includes electrodes, a separator and an electrolyte membrane.
[0041] It should be noted that the application methods shown in the following examples are only preferred application methods for the monomer / battery material. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention. In addition, unless otherwise specified, all reagents used in the following examples are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also easily obtained by those skilled in the art. The operation methods without specific conditions in the following examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0042] Example 1
[0043] An electrode sheet comprises a current collector and an electrode material covered on the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, and the electrode material further comprises a phosphorus-based polymer material; the mass proportion of the phosphorus-based polymer material in the electrode material is 0.08-20%; during the mixing process of the electrode material, the monomer and the initiator are added, and in-situ polymerization is performed to form the phosphorus-based polymer material; the monomer comprises a monomer A; the monomer A is at least one of the compounds shown in formula I,
[0044]
[0045] Among them, R is R 2 and R 3 Can be connected to -C=O or -O-; R 1 , R 2 , R 3 R is independently selected from any one of a chain or a ring with no, a substituent or a substituent; 4 and R 44 It is a chain saturated alkyl group which may be substituted.
[0046] R is an ester group, and the oxygen atom in the ester group is directly connected to phosphorus, which can make the charge flow in the molecule smoother and stabilize the entire molecular structure, thus having a better cooling effect. It can effectively improve the electrochemical properties of the battery, such as the first efficiency and capacity retention rate, and can improve the ability to suppress the temperature rise of the battery, further improve the safety of the battery, and extend the service life of the battery.
[0047] Optionally, the mass proportion of the phosphorus-based polymer material in the electrode material is 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any two of the values.
[0048] Preferably, the phosphorus-based polymer material accounts for 0.1-5% by mass in the electrode material.
[0049] Optionally, the mass proportion of the phosphorus-based polymer material in the electrode material is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 3%, 3.5%, 4%, 4.5%, 5% or any two of the values.
[0050] If the content of phosphorus-based polymer material is less than 0.08%, it is difficult to coat a thin layer of phosphorus-containing polymer material on the surface of the electrode active material particles, and the improvement in battery safety is not obvious; if the content of phosphorus-based polymer material is too much (greater than 20%), although it can greatly improve the safety of the battery, it will reduce the energy density and cycle performance of the battery, so it is preferably 0.08-20%, and more preferably 0.1-5%.
[0051] Optionally, R 1 ~R 3 Independently selected from chains, the chains are chains of 1 to 15 atoms.
[0052] Preferably, the chain is a chain of 1 to 10 atoms.
[0053] Preferably, the chain is a chain of 2 to 6 atoms.
[0054] Optionally, the chain includes at least one of a saturated carbon chain, an unsaturated carbon chain, a saturated hetero chain, and an unsaturated hetero chain.
[0055] Optionally, the atoms located on the chain are selected from at least one of C, S, N, O, P or Si.
[0056] Optionally, R 1 -R 3 Independently selected from rings, the chain is a ring of 3 to 18 atoms.
[0057] Optionally, the ring includes at least one of a single ring, a linked ring, a combined ring, a bridged ring or a spiro ring.
[0058] Optionally, the monocyclic ring includes a saturated carbocyclic ring, an unsaturated carbocyclic ring, a saturated heterocyclic ring, an unsaturated heterocyclic ring (-C=O), an aromatic carbocyclic ring, and an aromatic heterocyclic ring.
[0059] Optionally, the atoms located on the ring are selected from at least one of C, S, N, O, P, B or Si.
[0060] Optionally, R 1 , R 3 Any one independently selected from a chain of 1 to 15 atoms which is unsubstituted, substituted or unsubstituted.
[0061] Optionally, R 2 The moiety is selected from any one of a chain or a ring of 3 to 18 atoms which is free of substituents, has substituents or does not have substituents.
[0062] Optionally, R 2 The moiety is selected from any one of a chain or a ring of 6 to 10 atoms which is free of substituents, has substituents or does not have substituents.
[0063] Optionally, R 2 The base is selected from any one of phenyl, tolyl, ethylphenyl, acylbenzene, esterbenzene and amidebenzene.
[0064] Optionally, the substituents include: at least one of H, a halogen atom, =O, =S, an alkyl group, a heteroalkyl group, an alkenyl group, a heteroalkenyl group, an alkynyl group, a heteroalkynyl group, a hydroxyl group, a carbonyl group, an aldehyde group, a carbonate group, a haloformyl group, a carboxyl group, an ester group, a peroxy group, an amine group (primary amine, secondary amine, tertiary amine, quaternary ammonium salt), an imino group (C=N), an imide (C(=O)NC(=O)), an azo group, a nitrate ester (RONO2), a phosphate group, a thioether group, a disulfide group, a cyano group, a sulfonic acid group, a sulfonyl group, an amide group, a nitro group, a pyridyl group, an acyloxy group, a phenyl group, a benzyl group, a benzyloxy group, a phenoxy group, an acetyl group, a benzoyl group, and a benzyloxycarbonyl group.
[0065] Optionally, any H in the above substituents may be substituted by halogen.
[0066] Optionally, the halogen includes fluorine, chlorine, bromine, iodine, and astatine.
[0067] Preferably, the halogen is fluorine.
[0068] Preferably, R 3 For carbon chain.
[0069] R 3 It is a carbon chain, and the P atom is connected to the C atom on the chain by a bond, that is, there is a PC chain bond. Compared with all the bonds of all P atoms being directly connected to heteroatoms or rings, it can better promote the role of phosphorus groups and is more helpful to improve the safety of polymer materials.
[0070] Optionally, the monomer further comprises a monomer B; the monomer B is selected from at least one of the compounds shown in formula II,
[0071]
[0072] Among them, R 7 Selected from Any of the following;
[0073] A 1 , A 2 Indicates that the atoms in the ring / chain can be replaced by substituents;
[0074] Optionally, the substituent is a halogen atom or OLi;
[0075] Preferably, the halogen is fluorine.
[0076] A 1 , A 2 Indicates that the atoms in the ring / chain can be replaced by substituents.
[0077] Optionally, the R6 includes at least one of an ester group, an amide group or a phenylamide group.
[0078] Optionally, R6 contains at least one ester group or amide group.
[0079] Optionally, the chain or ring is the same as R 1 ~R 3 The chains or rings are the same.
[0080] Optionally, the substituent includes H, a halogen atom, =O, =S, an alkyl group, a heteroalkyl group, an alkenyl group, a heteroalkenyl group, an alkynyl group, a heteroalkynyl group, a hydroxyl group, a carbonyl group, an aldehyde group, a carbonate group, a haloformyl group, a carboxyl group, an ester group, a peroxy group, an amine group (primary amine, secondary amine, tertiary amine, quaternary ammonium salt), an imino group (C=N), an imide (C(=O)NC(=O)), an azo group, a nitrate ester (RONO 2 ), at least one of a phosphate group, a thioether group, a disulfide group, a cyano group, a sulfonic acid group, a sulfonyl group, an amide group, a nitro group, a pyridyl group, an acyloxy group, a phenyl group, a benzyl group, a benzyloxy group, a phenoxy group, an acetyl group, a benzoyl group, and a benzyloxycarbonyl group.
[0081] Optionally, the molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
[0082] Optionally, the molar ratio α of the monomer B to the monomer A is 0.01, 0.02, 0.025, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any ratio between any two ratios.
[0083] Optionally, the weight fractions of the components in the electrode material are: 80-98 parts of electrode active material, 0.2-10 parts of conductive agent, 0.2-10 parts of binder, and 0.1-20 parts of monomer.
[0084] Optionally, the electrode active material is 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts or any two parts.
[0085] Optionally, the conductive agent is 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two parts.
[0086] Optionally, the binder is 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two parts.
[0087] Optionally, the phosphorus-based polymer material is 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or any two parts.
[0088] Example 2
[0089] A method for preparing an electrode sheet, the electrode sheet is consistent with the electrode sheet described in Example 1, and will not be described in detail here. The preparation method is prepared by in-situ polymerization. Specifically, the preparation method includes:
[0090] (1) taking the above-mentioned portions of electrode active material, conductive agent, binder, monomer, and initiator, and mixing them uniformly to prepare a uniform mixed slurry;
[0091] (2) The uniformly mixed slurry is coated on the current collector and polymerized in situ to obtain the electrode sheet.
[0092] The temperature of the in-situ polymerization is 45 to 130° C., and the time of the in-situ polymerization is 0.1 to 60 min.
[0093] The mass fraction of the initiator in the mixed slurry is 0.001% to 2%;
[0094] The coating speed is 0.5 m / min to 75 m / min.
[0095] Optionally, the in situ polymerization temperature is 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C or any two of the above values.
[0096] Optionally, the in situ polymerization time is 0.1min, 0.2min, 0.3min, 0.4min, 0.5min, 0.6min, 0.7min, 0.8min, 0.9min, 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min min, 57min, 58min, 59min, 60min, or any two of the above values.
[0097] Optionally, the mass fraction of the initiator in the mixed slurry is 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any two of the values.
[0098] Preferably, the mass fraction of the initiator in the mixed slurry is 0.01% to 0.5%.
[0099] Optionally, the coating speed is 0.5 m / min, 0.6 m / min, 0.7 m / min, 0.8 m / min, 0.9 m / min, 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, 10 m / min, 20 m / min, 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 75 m / min or any two of the above values.
[0100] Optionally, the weight fractions of the components in the electrode material are: 80-98 parts of electrode active material, 0.2-10 parts of conductive agent, 0.2-10 parts of binder, and 0.1-20 parts of monomer.
[0101] Optionally, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl perbenzoate, and methyl ethyl ketone peroxide.
[0102] Optionally, the method for preparing the electrode sheet includes:
[0103] (1) adding electrode active materials, conductive agents, binders, monomers and initiators into a solvent and mixing them evenly to obtain a slurry with a certain fluidity; (2) coating the slurry in step (1) onto a current collector, controlling the coating speed to be 0.5 m / min to 75 m / min, baking at 45 to 130° C. to initiate in-situ polymerization of the monomers for a time of 0.1 to 60 min, and then rolling to obtain an electrode sheet.
[0104] Optionally, the solvent is an organic solvent.
[0105] Optionally, the organic solvent is selected from at least one of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, δ-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, polyethylene glycol, cyclopentane, dimethyl sulfoxide, triethylene glycol dimethyl ether, fluorinated 1,4-dimethoxybutane, bis(2,2,2-trifluoroethyl) ether, tetramethylsilane, and tetraethylene glycol dimethyl ether.
[0106] In the slurry of the present application, there is no limitation on the manner and order of adding the electrode active material, conductive agent, binder, monomer and initiator, and they can be added together or in batches.
[0107] Preferably, the electrode active material and the conductive agent are first added to the solvent, and then the monomer, the initiator and the binder are added after being mixed evenly.
[0108] This is because during the mixing process, the material will have a temperature rise, which will trigger in-situ polymerization of some monomers. In order to reduce polymerization, the monomer and initiator can be added in the latter order. In addition, when CMC and SBR are used as negative electrode binders, SBR is prone to demulsification due to long-term high-speed stirring, which will destroy its structure and reduce adhesion. Therefore, SBR is added last and stirred at a low speed.
[0109] Optionally, the slurry further comprises an auxiliary agent.
[0110] Optionally, the auxiliary agent is selected from at least one of inorganic oxide particles and fast ion conductors.
[0111] The inorganic particles are selected from SiO 2 、ZrO 2 、Al 2 O 3 、TiO 2 、BaTiO 3 、CeO 2 、CuO、ZnO、MnO、MnO 2 , silicates, aluminosilicates, borosilicates and formula A x B y O zAt least one inorganic particle selected from the group consisting of an oxygen-containing acid salt of, or any one of the functionalized above inorganic particles, wherein A is an alkali metal or an alkaline earth metal, B is selected from the group consisting of Al, Mn, Si, Ti, Zn, Zr, Fe and Cu, and x, y, z are the numbers of corresponding atoms so that the total charge of the oxygen-containing acid salt is 0.
[0112] Optionally, the fast ion conductor is an oxide solid electrolyte; the oxide solid electrolyte particles include at least one of the following compounds: Li NASICON structure 1+x1 Al x1 Ge 2-x1 (PO 4 ) 3 or its isomorphous heteroatom doped compound, Li 1+x2 Al x2 Ti 2-x2 (PO 4 ) 3 or its isomorphous heteroatom doped compounds, Li 3x3 La 2 / 3-x3 TiO 3 or its isomorphous heteroatom doped compound, Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O 3 or its isomorphous heteroatom doped compound, Li 2x4-y1 Sr 1-x4 Ta y1 Zr 1-y1 O 3 or its isomorphous heteroatom doped compounds, antiperovskite structured Li 3-2x5 M x5 HalO, Li 3 OCl or its isomorphous heteroatom doped compounds, 2Li with LISICON structure 4-x6 Si 1-x6 Px 6 O 4 or its isomorphous heteroatom doped compound, Li 14 ZnGe 4 O 16 or its isomorphous heteroatom doped compounds, garnet-structured Li 7-x7 La 3 Zr 2-x7 O 12 or its isomorphous heteroatom doped compound; wherein, 0 <x 1 ≤0.75,0 <x 2 ≤0.5, 0.06≤x 3 ≤0.14,0.25≤y 1≤1,x 4 =0.75y 1 , 0≤x 5 ≤0.01, 0.5≤x 6 ≤0.6; 0≤x 7 <1; M includes Mg 2+ , Ca 2+ , Sr 2+ Or Ba 2+ Any one or a combination of at least two of; Hal is Cl or I.
[0113] The electrode sheet includes a positive electrode sheet and / or a negative electrode sheet.
[0114] When preparing the positive electrode sheet, it is necessary to add positive electrode active materials and conductive agents and binders suitable for the positive electrode.
[0115] Optionally, the method for preparing the positive electrode sheet includes:
[0116] S1: Under the condition of dew point temperature ≤-45℃, add positive electrode active material, conductive agent, binder, polymerizable monomer and initiator into solvent and mix evenly in a mixer. During the mixing process, the material will have temperature rise, which will induce in-situ polymerization of some monomers to obtain a slurry with certain fluidity; S2: Coat the slurry in S1 onto the current collector, control the coating speed to 0.5m / min~75m / min, bake at 45~130℃ for 0.1~60min to induce in-situ polymerization of monomers, and then roll to obtain the positive electrode sheet.
[0117] Preferably, the dew point temperature is ≤-60°C.
[0118] Optionally, the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese oxide.
[0119] Optionally, the method for preparing the negative electrode sheet includes:
[0120] S3: adding negative electrode active material, conductive agent, binder, polymerizable monomer and initiator into solvent and mixing evenly in a mixer to obtain a slurry with certain fluidity; S4: coating the slurry in S3 onto the current collector, controlling the coating speed to be 0.5m / min~75m / min, baking at 45~130℃ for 0.1~60min to initiate in-situ polymerization of the monomer, and then rolling to obtain the negative electrode sheet.
[0121] Optionally, the negative electrode is at least one of graphite, silicon, soft carbon, hard carbon, silicon-carbon composite material, silicon-oxygen-carbon, lithium titanate, mesophase carbon microbeads, molybdenum disulfide, silicon oxide, silicon, metallic lithium or metallic lithium alloy.
[0122] It should be noted that in the technical solution provided in the present application, no matter what synthesis method or process is used, a phosphorus-based polymer material as shown in Formula III, Formula IV or Formula V can be formed by the reaction of monomer A itself or the reaction between monomer A and monomer B. If in certain special cases, other products are obtained by the reaction of monomer A itself or monomer A and monomer B, these products are also within the scope of protection of the present application.
[0123] Example 3
[0124] A battery comprises at least one of the electrode sheets as described above and the electrode sheets obtained according to any of the preparation methods as described above.
[0125] The battery can be a liquid battery, a hybrid solid-liquid battery or an all-solid-state battery (hybrid solid-liquid batteries and all-solid-state batteries are collectively referred to as solid-state batteries). In practical applications, the electrolyte can be an existing commercial electrolyte used for lithium secondary batteries, or it can be independently configured. The present invention does not specifically limit its composition and ratio.
[0126] Optionally, the battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0127] Optionally, the battery further has a packaging casing.
[0128] Optionally, the electrolyte includes lithium salt, electrolyte additives and organic solvents.
[0129] Optionally, the lithium salt is selected from lithium hexafluorophosphate (LiPF 6 ), Lithium Bis(trifluoromethanesulfonate)imide (LiN(CF 3 SO 2 ) 2 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium trifluoromethylbenzenesulfonate, lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiCF 3 SO 2 ), one or more of lithium difluorophosphate, lithium difluorobisoxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0130] Optionally, the mass fraction of the lithium salt in the electrolyte is 5% to 30%.
[0131] Optionally, the organic solvent is selected from at least one of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, δ-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, polyethylene glycol, cyclopentane, dimethyl sulfoxide, triethylene glycol dimethyl ether, fluorinated 1,4-dimethoxybutane, bis(2,2,2-trifluoroethyl) ether, tetramethylsilane, and tetraethylene glycol dimethyl ether.
[0132] Optionally, the mass fraction of the organic solvent in the electrolyte is 1% to 90%.
[0133] Furthermore, the electrolyte additive is a commercial additive, including one or more combinations of fluoroethylene carbonate, vinylene carbonate, trimethyl phosphate, triethyl phosphate, succinic anhydride, 18-crown ether-6, triphenyl phosphite, vinyl ethylene carbonate, trimethyl borate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, tributyl phosphate, biphenyl, vinyl sulfite, difluorodiphenylsilane, lithium bis(fluorosulfonyl)imide, tributyl borate, ethoxypentafluorocyclotriphosphazene, vinyl sulfate, lithium nitrate, 1,3-propane sultone, lithium difluorophosphate, diethyl sulfite, and succinonitrile.
[0134] Optionally, the diaphragm is at least one of a polyolefin diaphragm, a cellulose diaphragm, a polyimide diaphragm, a polyamide diaphragm, an aramid diaphragm, a PET non-woven fabric diaphragm, a ceramic coated diaphragm, a solid electrolyte coated diaphragm, and a PVDF coated diaphragm.
[0135] Optionally, the packaging shell is any one of a soft-package aluminum-plastic film, a steel shell, an aluminum shell, and a cylinder.
[0136] Example 4
[0137] 1. Preparation of positive electrode slurry
[0138] The positive electrode active material, conductive agent, binder, and fast ion conductor are mixed according to the data ratios listed in Table 1 C1-C6 and added to N-methylpyrrolidone. The mass fraction of the solvent in the total slurry is 65%. The mixture is stirred evenly to obtain a positive electrode slurry with a certain fluidity. The slurry is coated on the aluminum current collector. The surface capacity of the control electrode is 5 mAh / cm 2, blast drying, roller pressing, and named C1, C2, ... C6. Among them, the conductive agent is carbon nanotubes and conductive carbon black (CNT + Super-P, the mass ratio of the two is 1:2), and the binder is polyvinylidene fluoride (PVDF). The ratio is the mass ratio of the positive electrode active material, the binder, the conductive agent, and the fast ion conductor.
[0139] The positive electrode material is LiCoO 2 (abbreviated as LCO), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (abbreviated as NCM811), LiNi 0.8 Co 0.15 Al 0.05 O 2 (abbreviated as NCA); the fast ion conductor is Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 (Abbreviated as LATP).
[0140] Table 1 Components and ratios of positive electrode slurry
[0141]
[0142]
[0143] 2. Preparation of negative electrode slurry
[0144] The negative electrode active material, conductive agent and binder were added into deionized water according to the data listed in Table 2 and mixed and stirred evenly, accounting for 42% of the total slurry, to obtain a negative electrode slurry with a certain fluidity, which was coated on the copper current collector to control the electrode surface capacity to 5.3 mAh / cm 2 , blast drying, roller pressing, named F1, F2, F3, F5; or directly use metal lithium as the negative electrode F4. The ratio is the mass ratio of the negative electrode active material, binder, and conductive agent.
[0145] Carboxymethyl cellulose is abbreviated as CMC and styrene-butadiene rubber is abbreviated as SBR.
[0146] Table 2 Components and ratios of negative electrode slurry
[0147] serial number Negative electrode active material Conductive agent Binder Proportion F1 Silicon Oxycarbon 450 CNT+Super-P CMC+SBR 95:2.5:2.5 F2 Natural graphite CNT+Super-P CMC+SBR 95:2.5:2.5 F3 Silicon Carbon CNT+Super-P CMC+SBR 96:2:2 F4 Lithium Metal —— —— —— F5 Silicon Oxycarbon 450 CNT+Super-P CMC+SBR 96:2:2
[0148] The negative electrode active material is silicon oxygen carbon 450 (SiOC, specific capacity 450mAh / g). The silicon carbon material comes from Liyang Tianmu Pioneer Battery Material Technology Co., Ltd., SL450A-SOC; the silicon oxygen carbon material comes from BYD New Energy Materials Co., Ltd., S450-2A; the binder is sodium carboxymethyl cellulose and styrene butadiene rubber (CMC+SBR).
[0149] 3. Diaphragm
[0150] Table 3 Diaphragm
[0151] serial number Diaphragm Specifications / Compartment S1 <![CDATA[PE / Al 2 THE 3 ]]> 12μm+2μm S2 <![CDATA[Al 2 A 3 / PE / Al 2 A 3 / PVDF]]> 2μm+12μm+2μm+1μm S3 PE / LATP 12μm+2μm S4 PP 16μm
[0152] 4. Electrolyte
[0153] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.
[0154] For ease of understanding, the abbreviations and corresponding substances mentioned in the above text are explained, specifically: ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC); lithium nitrate (LiNO3), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), lithium tetrafluoro oxalate phosphate (LiPC 2 O 2 F 4 ), 1,4-dimethoxybutane fluoride (FDMB), 1,3-propane sultone (1,3-PS), lithium difluorophosphate (LiPO 2 F 2 ), vinylene carbonate (VC); lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalatoborate) (LiBOB), lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluoromethylsulfonyl)imide (LiFSI); azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO).
[0155] Table 4 Preparation of electrolyte
[0156]
[0157]
[0158] Preparation method of blank battery:
[0159] As shown in Table 5-1, the negative electrode active material, conductive agent and binder are mixed evenly to form a negative electrode slurry, which is then coated on copper foil. The coating speed is controlled, and air drying and roller pressing are performed to obtain a blank negative electrode sheet. Alternatively, a 50μm metal lithium foil is pressed on the copper foil to serve as a metal lithium negative electrode.
[0160] As shown in Table 5-1, the positive electrode active material, binder, conductive agent and fast ion conductor are respectively mixed evenly to form a positive electrode slurry, which is then coated on an aluminum foil, dried by air blast and rolled to obtain a blank positive electrode sheet.
[0161] As shown in Table 5-1, the negative electrode sheets, positive electrode sheets and separators containing the battery materials are stacked and baked to obtain dry cells. The cells are then placed in a packaging shell, and the electrolyte is injected. The batteries are packaged and left to stand at room temperature for 12 hours to allow the cells to be fully soaked, thereby obtaining blank solid-state batteries containing battery materials.
[0162] Experimental Example 1-1
[0163] Monomer A1: Monomer B1:
[0164] A1 is an existing substance, CAS: 222978-54-3. H NMR spectrum of monomer A1 1 H NMR (300MHz, DMSO, δppm): 2.97 (d, 2H), 4.19 (m, 4H), 4.31 (m, 2H), 4.38 (m, 2H), 1.36 (t, 6H), 2.01 (s, 3H), 6.48 (s, H), 6.40 (s, H).
[0165] Preparation method of monomer B1: 0.04 mol (CAS: 1433993-67-9), 0.04mol (CAS: 30674-80-7) and 25 ml of dichloromethane were added into a 50 ml three-necked flask and stirred for 3 hours. A dichloromethane solution containing 0.06 g of stannous isooctanoate was added dropwise through a constant pressure funnel. The mixture was reacted at 5°C for 8 hours. The solvent was then removed by reduced pressure distillation at 25°C to obtain monomer B1.
[0166] H NMR spectrum of monomer B1 1 H NMR (300MHz, DMSO, δppm): 6.76 (s, 1H), 5.27 (m, 1H), 4.75 (dd, 1H), 4.50 (dd, 1H), 4.33 (dd, 1H), 4.08 (dd, 1H), 4.58 (t, 2H), 3.15 (t, 2H), 2.01 (s, 3H), 6.48 (s, H), 6.40 (s, H).
[0167] Preparation method of negative electrode sheet 1-1 and battery 1-1:
[0168] As shown in Table 5, monomers A1, B1 and initiator AIBN were mixed into the prepared negative electrode slurry F1 and mixed evenly, coated on copper foil, the coating speed was controlled, in-situ polymerized at a certain temperature for a period of time, dried with air, and rolled to obtain a negative electrode sheet 1-1.
[0169] The positive electrode slurry C1 is coated on an aluminum foil, dried with air, and rolled to obtain a positive electrode sheet 1-1.
[0170] The negative electrode sheet 1-1, the positive electrode sheet 1-1 and the separator S1 containing the battery material are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then the electrolyte E1 is injected and allowed to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 1-1 containing battery materials.
[0171] Experimental Example 1-2
[0172] Preparation method of negative electrode sheet 1-2 and battery 1-2:
[0173] The preparation method of the negative electrode sheet 1-2 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced by the monomer A1, and the remaining steps are the same to obtain the negative electrode sheet 1-2;
[0174] The preparation method of battery 1-2 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced by negative electrode plate 1-2, and the remaining steps are the same to obtain battery 1-2.
[0175] Comparative Examples 1-3
[0176] Monomer D1:
[0177] The difference between the monomer D1 and the monomer A1 is that D1 does not contain a phosphorus group.
[0178] Preparation method of negative electrode sheet 1-3 and battery 1-3:
[0179] The preparation method of the negative electrode sheet 1-3 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer D1, and the remaining steps are the same to obtain the negative electrode sheet 1-3;
[0180] The preparation method of battery 1-3 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-3, and the remaining steps are the same to obtain battery 1-3.
[0181] Comparative Examples 1-4
[0182] Monomer D2:
[0183] The difference between the monomer D2 and the monomer A1 is that D2 does not contain a phosphorus group.
[0184] Preparation method of negative electrode sheet 1-4 and battery 1-4:
[0185] The preparation method of the negative electrode sheet 1-4 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer D2, and the remaining steps are the same to obtain the negative electrode sheet 1-4;
[0186] The preparation method of battery 1-4 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-4, and the remaining steps are the same to obtain battery 1-4.
[0187] Comparative Examples 1-5
[0188] Preparation method of negative electrode sheet 1-5 and battery 1-5:
[0189] The preparation method of the negative electrode sheet 1-5 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced by the monomer B1, and the remaining steps are the same to obtain the negative electrode sheet 1-5;
[0190] The preparation method of battery 1-5 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced by negative electrode plate 1-5, and the remaining steps are the same to obtain battery 1-5.
[0191] Comparative Examples 1-6
[0192] Monomer K1:
[0193] Preparation method of negative electrode sheet 1-6 and battery 1-6:
[0194] The preparation method of the negative electrode sheet 1-6 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced with monomers A1 and K1, and the remaining steps are the same to obtain the negative electrode sheet 1-6;
[0195] The preparation method of battery 1-6 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced with negative electrode plate 1-6. The remaining steps are the same to obtain battery 1-6.
[0196] Comparative Examples 1-7
[0197] Preparation method of negative electrode sheet 1-7 and battery 1-7:
[0198] The preparation method of the negative electrode sheet 1-7 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the initiator AIBN in Experimental Example 1-1 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-7;
[0199] The preparation method of battery 1-7 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced with negative electrode plate 1-7. The remaining steps are the same to obtain battery 1-7.
[0200] Due to the lack of initiator, monomer A1 and monomer B1 do not polymerize.
[0201] Comparative Examples 1-8
[0202] Preparation method of negative electrode sheet 1-8 and battery 1-8:
[0203] The preparation method of the negative electrode sheet 1-8 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the initiator AIBN in Experimental Example 1-2 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-8;
[0204] The preparation method of battery 1-8 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-8, and the remaining steps are the same to obtain battery 1-8.
[0205] Due to the lack of initiator, monomer A1 does not polymerize.
[0206] Comparative Examples 1-9
[0207] Monomer K2:
[0208] Preparation method of positive electrode sheet 1-9, negative electrode sheet 1-9 and battery 1-9:
[0209] The preparation method of the positive electrode sheet 1-9 is the same as the preparation method of the negative electrode sheet 1-2, that is, the positive electrode sheet 1-9 is obtained;
[0210] The preparation method of the negative electrode sheet 1-9 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-9;
[0211] A2 was replaced with the same mass of K2 and acrylonitrile (the mass ratio of K2 to acrylonitrile was 2:1), and added to the electrolyte E1 with AIBN, and in situ polymerization was performed to obtain the gel polymer electrolyte E1-9.
[0212] The preparation method of battery 1-9 is substantially the same as that of battery 1-2. The negative electrode sheet 1-2 is replaced by the negative electrode sheet 1-9, and the electrolyte E1 is replaced by the electrolyte E1-9. The remaining steps are the same to obtain battery 1-9.
[0213] Comparative Examples 1-10
[0214] Monomer K3:
[0215] Preparation method of negative electrode sheet 1-10 and battery 1-10:
[0216] The preparation method of the negative electrode sheet 1-10 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-10;
[0217] The preparation method of battery 1-10 is roughly the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-10, and the monomer K3 and the initiator AIBN are added to the electrolyte E1. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell, and the above-mentioned electrolyte is injected into the battery cell and polymerized in situ. The remaining steps are the same to obtain battery 1-10.
[0218] Comparative Examples 1-11
[0219] Preparation method of negative electrode sheet 1-11 and battery 1-11:
[0220] The preparation method of the negative electrode sheet 1-11 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-11;
[0221] The preparation method of battery 1-11 is roughly the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-11, and the monomer A1 and the initiator AIBN are added to the electrolyte E1. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell, and the above-mentioned electrolyte is injected into the battery cell and polymerized in situ. The remaining steps are the same to obtain battery 1-11.
[0222] Comparative Examples 1-12
[0223] Preparation method of negative electrode sheet 1-12 and battery 1-12:
[0224] The preparation method of the negative electrode sheet 1-12 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomers A1 and AIBN are not added. The remaining steps are the same. After obtaining the negative electrode sheet, a solution containing A1 and AIBN is applied to the surface of the negative electrode sheet, and in-situ polymerization is performed at a certain temperature to obtain a negative electrode sheet 1-12 having a phosphorus-based polymer material on the surface.
[0225] The preparation method of battery 1-12 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-12, and the remaining steps are the same to obtain battery 1-12.
[0226] Comparative Examples 1-13
[0227] Preparation method of negative electrode sheet 1-13 and battery 1-13:
[0228] The preparation method of the negative electrode sheet 1-13 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-13;
[0229] A solution containing A1 and AIBN is applied to the surface of the membrane S1, and in-situ polymerization is performed to obtain a membrane 1-13 having a phosphorus-based polymer material on the surface;
[0230] The preparation method of battery 1-13 is substantially the same as that of battery 1-2. The negative electrode plate 1-2 is replaced by the negative electrode plate 1-13, and the diaphragm S1 is replaced by the diaphragm 1-13. The remaining steps are the same to obtain battery 1-13.
[0231] Comparative Examples 1-14
[0232] Preparation method of negative electrode sheet 1-14, positive electrode sheet 1-14 and battery 1-14:
[0233] The preparation method of the negative electrode sheet 1-14 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-14;
[0234] Applying a solution containing A1 and AIBN to the surface of the positive electrode sheet 1-2, and polymerizing in situ to obtain a positive electrode sheet 1-14 having a phosphorus-based polymer material on the surface;
[0235] The preparation method of battery 1-14 is substantially the same as that of battery 1-2, except that the negative electrode sheet 1-2 is replaced by the negative electrode sheet 1-13, and the positive electrode sheet 1-2 is replaced by the positive electrode sheet 1-14. The remaining steps are the same to obtain battery 1-14.
[0236] Comparative Examples 1-15
[0237] Preparation method of negative electrode sheet 1-15 and battery 1-15:
[0238] The monomer A1 is polymerized in situ under the action of initiator AIBN to obtain polymer material G1-15, and then the polymer material G1-15 is mixed into the negative electrode slurry F1 and mixed evenly. The remaining steps are roughly the same as the preparation method of the negative electrode plate 1-2 to obtain the negative electrode plate 1-15.
[0239] The preparation method of battery 1-15 is substantially the same as that of battery 1-2. The negative electrode plate 1-2 is replaced with the negative electrode plate 1-15. The remaining steps are the same to obtain battery 1-15.
[0240] Comparative Examples 1-16
[0241] Preparation method of electrolyte E1-16, negative electrode sheet 1-16 and battery 1-16:
[0242] Monomer A1 and AIBN were added to E1, stirred to form a uniform solution, and then polymerized in situ to obtain polymer electrolyte E1-16.
[0243] The preparation method of the negative electrode sheet 1-16 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-16;
[0244] The preparation method of battery 1-16 is substantially the same as that of battery 1-2. The negative electrode plate 1-2 is replaced by the negative electrode plate 1-16, and the electrolyte E1 is replaced by the electrolyte E1-16. The remaining steps are the same to obtain battery 1-16.
[0245] Comparative Examples 1-17
[0246] Monomer K4: flame retardant trimethyl phosphate (TMP)
[0247] The preparation method of battery 1-17 is substantially the same as that of blank battery 1, except that K4 accounting for 1.2% by mass of the negative electrode active material is added to the electrolyte E1, and the remaining steps are the same to obtain battery 1-17.
[0248] Comparative Examples 1-18
[0249] Monomer K5:
[0250] The difference between monomer K5 and monomer A1 is that there is a pure carbon chain between P and the double bond.
[0251] Preparation method of negative electrode sheet 1-18 and battery 1-18:
[0252] The preparation method of the negative electrode sheet 1-10 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer K5, and the remaining steps are the same, to obtain the negative electrode sheet 1-18;
[0253] The preparation method of battery 1-18 is substantially the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-18, and the remaining steps are the same to obtain battery 1-18.
[0254] Comparative Examples 1-19
[0255] Preparation method of negative electrode sheet 1-19 and battery 1-19:
[0256] The preparation method of the negative electrode sheet 1-19 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that 1.2% of the monomer A1 of the electrode active material is replaced with 0.07% of the monomer A1, and the amount of the initiator is adjusted accordingly according to the amount of the monomer A1. The remaining steps are the same to obtain the negative electrode sheet 1-19.
[0257] The preparation method of battery 1-19 is substantially the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-19, and the remaining steps are the same to obtain battery 1-2.
[0258] Comparative Examples 1-20
[0259] Preparation method of negative electrode sheet 1-20 and battery 1-20:
[0260] The preparation method of the negative electrode sheet 1-20 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that 1.2% of the monomer A1 of the electrode active material is replaced with 21% of the monomer A1, and the amount of the initiator is adjusted accordingly according to the amount of the monomer A1. The remaining steps are the same to obtain the negative electrode sheet 1-20.
[0261] The preparation method of battery 1-20 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-20, and the remaining steps are the same to obtain battery 1-2.
[0262] Experimental Example 2-1
[0263] Monomer A2: Monomer B2:
[0264] A2 is an existing substance, CAS: 60161-88-8; H NMR spectrum of monomer A2 1 H NMR (300MHz, DMSO, δppm): 4.63 (d, 2H), 4.19 (m, 4H), 1.36 (t, 6H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).
[0265] Preparation method of monomer B2:
[0266]
[0267] Under nitrogen protection, 0.2 mmol of raw material 1 and 2 mL of dry THF were added to a 25 mL Schlenk reaction tube, cooled to -78 °C, n-BuLi hexane solution was added dropwise, stirred for 30 min, 0.2 mmol of p-bromobenzyl bromide was added dropwise, stirred for 30 min after the addition, gradually returned to room temperature, reacted at room temperature for 30 min, added water twice to quench the reaction, extracted with DCM, dried, and distilled under reduced pressure to obtain intermediate 2.
[0268] 0.2 mmol of intermediate 2, 5 mol% of Pd2(dba)3, 10 mol% of rac-BINAP and 7.0 eq of t-BuONa were placed in a 25 ml Schlenk reaction tube, replaced with nitrogen, 2 mL of dry toluene and 1.5 eq of benzophenone imine were added, reacted at 120 °C for 24 h, filtered, the filter cake was washed with DCM, the mother liquor was distilled under reduced pressure, and column chromatography was performed to obtain intermediate 3.
[0269] Take 0.2 mmol of intermediate 3 and 2 mL of dry THF, add acryloyl chloride dropwise, stir and react at room temperature for 30 min, add water to quench, extract with DCM, dry, distill under reduced pressure, and obtain product 4, i.e. monomer B2, by column chromatography.
[0270] H NMR spectrum of monomer B2 1 H NMR (300MHz, DMSO, δppm): 9.54 (s, 1H), 3.57 (m, 1H), 4.32 (m, 1H), 4.22 (m, 1H), 2.5 (dt, 1H), 2.25 (dt , 1H), 7.69(d, 2H), 7.17(d, 2H), 2.94(dt, 1H), 2.69(dt, 1H), 1.98(s, 3H), 5.79(s, 1H), 5.72(s, 1H).
[0271] Preparation method of negative electrode sheet 2-1 and battery 2-1:
[0272] As shown in Table 5, monomers A2, B2 and initiator AIBN were mixed into the prepared negative electrode slurry F2 and mixed evenly, and then coated on copper foil. The coating speed was controlled, and in-situ polymerization was performed at a certain temperature for a period of time, and then the mixture was dried with air blast and rolled to obtain a negative electrode sheet 2-1.
[0273] The positive electrode slurry C2 is coated on an aluminum foil, dried by air blast, and rolled to obtain a positive electrode sheet 2-1.
[0274] The negative electrode sheet 2-1, the positive electrode sheet 2-1 and the separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then the electrolyte E2 is injected. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 2-1 containing battery materials.
[0275] Experimental Example 2-2
[0276] Preparation method of negative electrode sheet 2-2 and battery 2-2:
[0277] The preparation method of the negative electrode sheet 2-2 is substantially the same as the preparation method of the negative electrode sheet 2-1, except that the monomers A2 and B2 are replaced by the monomer A2, and the remaining steps are the same to obtain the negative electrode sheet 2-2;
[0278] The preparation method of battery 2-2 is substantially the same as that of battery 2-1, except that negative electrode plate 2-1 is replaced by negative electrode plate 2-2, and the remaining steps are the same to obtain battery 2-2.
[0279] Comparative Examples 2-3
[0280] Preparation method of negative electrode sheet 2-3 and battery 2-3:
[0281] The preparation method of the negative electrode sheet 2-3 is substantially the same as the preparation method of the negative electrode sheet 2-1, except that the monomers A2 and B2 and the initiator AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 2-3;
[0282] The preparation method of battery 2-3 is roughly the same as that of battery 2-1. The negative electrode plate 2-1 is replaced with the negative electrode plate 2-3, and the monomers A2, B2 and initiator AIBN are added to the electrolyte E2. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell. The above electrolyte is injected into the battery cell and polymerized in situ. The remaining steps are the same to obtain battery 2-3.
[0283] Experimental Example 3-1
[0284] Monomer A3: Monomer B3:
[0285] Preparation method of monomer A3: (CAS: 3095-95-2) and (CAS: 924-42-5) undergoes esterification reaction under heating and acid catalyst conditions to obtain monomer A3;
[0286] Preparation method of monomer B3: (CAS: 75732-49-9) and (CAS: 79-41-4) undergoes esterification reaction under acid catalysis to obtain monomer B3.
[0287] The hydrogen nuclear magnetic resonance spectrum of monomer A3 is 1H NMR (300 MHz, DMSO, δ ppm): 9.38 (s, 1H), 2.97 (d, 2H), 5.75 (s, 2H), 4.19 (m, 4H), 1.36 (t, 6H), 6.48 (dd, 1H), 6.09 (d, 1H), 5.74 (s, 1H).
[0288] The hydrogen nuclear magnetic resonance spectrum of monomer B3 is 1H NMR (300 MHz, DMSO, δ ppm): 2.99 (q, 1H), 4.32 (m, 1H), 4.22 (m, 1H), 2.50 (dt, 1H), 2.25 (dt, 1H), 4.61 (m, 1H), 1.3 (m, 1H), 1.75 (m, 1H), 1.50 (m, 1H), 1.80 (m, 1H), 1.55 (m, 1H), 1.63 (m, 1H), 1.38 (m, 1H), 1.53 (m, 1H), 1.43 (m, 1H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).
[0289] Preparation method of negative electrode sheet 3-1 and battery 3-1:
[0290] As shown in Table 5, monomers A3, B3 and initiator AIBN were mixed into the negative electrode slurry F3 and mixed evenly, coated on copper foil, the coating speed was controlled, in-situ polymerized at a certain temperature for a period of time, dried with air, and rolled to obtain the negative electrode sheet 3-1.
[0291] The positive electrode slurry C3 is coated on an aluminum foil, dried by air blast, and rolled to obtain a positive electrode sheet 3-1.
[0292] The negative electrode sheet 3-1, the positive electrode sheet 3-1 and the separator S3 containing the battery material are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then the electrolyte E3 is injected. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 3-1 containing battery materials.
[0293] Experimental Example 3-2
[0294] Preparation method of negative electrode sheet 3-2 and battery 3-2:
[0295] The preparation method of the negative electrode sheet 3-2 is substantially the same as the preparation method of the negative electrode sheet 3-1, except that the monomers A3 and B3 are replaced by the monomer A3, and the remaining steps are the same to obtain the negative electrode sheet 3-2;
[0296] The preparation method of battery 3-2 is substantially the same as that of battery 3-1, except that negative electrode plate 3-1 is replaced by negative electrode plate 3-2, and the remaining steps are the same to obtain battery 3-2.
[0297] Experimental Example 4-1
[0298] Monomer A4: Monomer B4:
[0299] Preparation method of monomer A4: The preparation method of A4 is as shown in Example 3. (CAS: 3095-95-2) and (CAS: 19243-95-9) was obtained by reaction.
[0300] Preparation method of monomer B4:
[0301]
[0302] 0.2 mmol of raw material 1 and 1.5 eq of NBS were placed in a 25 mL Schlenk reaction tube, 2 mL of dry DCM was added, and the mixture was stirred at room temperature for 5 h. Water was added to quench the mixture, and the mixture was extracted with DCM. The mixture was dried, evaporated under reduced pressure, and column chromatography was performed to obtain intermediate 2.
[0303] Under nitrogen protection, 0.2 mmol of raw material 2, 1.2 eq of raw material sodium alcoholate, and 2 mL of dry tetrahydrofuran were added to a 25 mL reaction tube. After the addition was complete, the reaction was carried out for 5 h, and the reaction was quenched with water. The reaction was extracted with DCM, dried, and distilled under reduced pressure. The product 3, i.e., monomer B4, was obtained by column chromatography.
[0304] Nuclear magnetic resonance hydrogen spectrum of monomer A4: 1H NMR (300 MHz, DMSO, δ ppm): 9.54 (s, 1H), 7.20 (d, 2H), 7.55 (d, 2H), 3.17 (d, 2H), 4.19 (m, 4H), 1.36 (t, 6H), 1.98 (s, 3H), 5.79 (s, 1H), 5.72 (s, 1H).
[0305] The hydrogen nuclear magnetic resonance spectrum of monomer B4 is 1H NMR (300 MHz, DMSO, δ ppm): 5.93 (d, 1H), 5.10 (dq, 1H), 3.71 (t, 1H), 3.46 (dd, 1H), 4.27 (t, 2H), 3.65 (t, 2H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).
[0306] Preparation method of negative electrode sheet 4-1 and battery 4-1:
[0307] As shown in Table 5, monomers A4, B4 and initiator AIBN were mixed into the negative electrode slurry F3 and mixed evenly, coated on copper foil, the coating speed was controlled, in-situ polymerized at a certain temperature for a period of time, dried with air, and rolled to obtain the negative electrode sheet 4-1.
[0308] The positive electrode slurry C3 is coated on an aluminum foil, dried by air blast, and rolled to obtain a positive electrode sheet 4-1.
[0309] The negative electrode sheet 4-1, the positive electrode sheet 4-1 and the separator S1 containing the battery material are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then the electrolyte E4 is injected. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 4-1 containing battery materials.
[0310] Experimental Example 4-2
[0311] Preparation method of negative electrode sheet 4-2 and battery 4-2:
[0312] The preparation method of the negative electrode sheet 4-2 is substantially the same as the preparation method of the negative electrode sheet 4-1, except that the monomers A4 and B4 are replaced by the monomer A4, and the remaining steps are the same to obtain the negative electrode sheet 4-2;
[0313] The preparation method of battery 4-2 is substantially the same as that of battery 4-1, except that negative electrode plate 4-1 is replaced by negative electrode plate 4-2, and the remaining steps are the same to obtain battery 4-2.
[0314] Experimental Example 5-1
[0315] Monomer A5: Monomer B5:
[0316] Preparation method of monomer A5: A5 is an existing substance, CAS: 45116-57-2. Nuclear magnetic resonance hydrogen spectrum of monomer A5 1 HNMR (300MHz, DMSO, δppm): 4.63 (d, 2H), 4.19 (m, 4H), 1.36 (t, 6H), 6.12 (dd, 1H), 6.41 (d, 1H), 5.83 (d, 1H).
[0317] Preparation method of monomer B5: (CAS: 10429-10-4) was hydrolyzed under alkaline conditions. 1H NMR (300 MHz, DMSO, δ ppm) of B5: 5.07 (s, 1H), 5.34 (d, 1H), 5.09 (s, 1H).
[0318] Preparation method of positive electrode sheet 5-1 and battery 5-1:
[0319] According to the data listed in Table 5, under the condition of dew point ≤-30°C, monomers A5, B5 and initiator AIBN are mixed into the prepared positive electrode slurry C3 and mixed evenly, coated on aluminum foil, the coating speed is controlled, in-situ polymerization is carried out at a certain temperature for a period of time, air drying is carried out, and roller pressing is carried out to obtain the positive electrode sheet 5-1.
[0320] The negative electrode slurry F3 is coated on a copper foil, dried by air blast, and rolled to obtain a negative electrode sheet 5-1.
[0321] The positive electrode sheet 5-1, negative electrode sheet 5-1 and separator S2 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E5. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 5-1 containing battery materials.
[0322] Experimental Example 5-2
[0323] Preparation method of positive electrode sheet 5-2 and battery 5-2:
[0324] The preparation method of the positive electrode sheet 5-2 is substantially the same as the preparation method of the positive electrode sheet 5-1, except that the monomers A5 and B5 are replaced by the monomer A5, and the remaining steps are the same to obtain the positive electrode sheet 5-2;
[0325] The preparation method of battery 5-2 is substantially the same as that of battery 5-1, except that the positive electrode sheet 5-1 is replaced by the positive electrode sheet 5-2, and the remaining steps are the same to obtain battery 5-2.
[0326] Comparative Example 5-3
[0327] Preparation method of positive electrode sheet 5-3 and battery 5-3:
[0328] The preparation method of the positive electrode sheet 5-3 is substantially the same as the preparation method of the positive electrode sheet 5-1, except that the monomers A5, B5 and BPO are not added, and the remaining steps are the same to obtain the positive electrode sheet 5-3;
[0329] The preparation method of battery 5-3 is roughly the same as that of battery 5-1, except that the positive electrode plate 5-1 is replaced by the positive electrode plate 5-3, and monomers A5, B5 and initiator AIBN are added to the electrolyte E5; the positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell, the above-mentioned electrolyte is injected into the battery cell, and in-situ polymerization is carried out. The remaining steps are the same to obtain battery 5-3.
[0330] Comparative Example 5-4
[0331] Preparation method of positive electrode sheet 5-4 and battery 5-4:
[0332] The preparation method of the positive electrode sheet 5-4 is substantially the same as the preparation method of the positive electrode sheet 5-2, except that the monomer A5 and the initiator AIBN are not added, and the remaining steps are the same to obtain the positive electrode sheet 5-4;
[0333] The preparation method of battery 5-4 is substantially the same as that of battery 5-3, except that positive electrode plate 5-3 is replaced by positive electrode plate 5-4, and A5 and B5 added to electrolyte E5 are replaced by A5. The remaining steps are the same to obtain battery 5-4.
[0334] Experimental Example 6-1
[0335] Monomer A6: Monomer B6:
[0336] Preparation method of monomer A6: The preparation method of A6 is as shown in Example 3. (CAS: 3095-95-2) and (CAS: 764-48-7) was obtained by reaction.
[0337] Preparation of monomer B6: Add 0.2 mmol and 2mL dry dichloromethane, freeze with liquid nitrogen, replace with nitrogen in vacuum, return to room temperature, add 0.2mmol NBS under nitrogen protection, heat to 40℃ and stir for 8h, terminate the reaction, distill under reduced pressure, and obtain the intermediate of sulfonate substrate olefin double bond α-position bromine substitution by column chromatography. Then put the bromine-substituted intermediate in the previous step into 2mL dichloromethane, add benzyltriethylammonium chloride (TEBAC), 0.2mmol NaF, and stir for 8h at 40℃. Cool to room temperature, add 5mL water, extract with 3×5mL dichloromethane, combine the organic phases, wash with saturated NaCl, dry with anhydrous sodium sulfate, filter, distill under reduced pressure, and obtain the fluorinated sulfonate intermediate by column chromatography.
[0338] Under nitrogen protection, 0.2 mmol 200 μL (1M) borane tetrahydrofuran complex was added dropwise, stirred at room temperature for 30 min, 70 μL 3M sodium hydroxide was added first, and then 20 μL hydrogen peroxide (30% wt) was added, stirred for 30 min, 5 mL dichloromethane and 5 mL water were added, 3×5 mL dichloromethane was extracted, the organic phases were combined, washed with saturated NaCl, dried over anhydrous sodium sulfate, filtered, distilled under reduced pressure, and column chromatography was performed to obtain
[0339] Under nitrogen protection, 0.2 mmol of 0.2 mmol of acryloyl chloride was added dropwise to 2 mL of dry dichloromethane, stirred at room temperature for 30 min, the reaction was terminated, 5 mL of water was added, and the mixture was extracted with 3×5 mL of dichloromethane. The organic phases were combined, washed with saturated NaCl, dried over anhydrous sodium sulfate, filtered, distilled under reduced pressure, and the product was obtained by column chromatography.
[0340] Nuclear magnetic resonance hydrogen spectrum of monomer A6: 1H NMR (300 MHz, DMSO, δ ppm): 2.97 (d, 2H), 4.19 (m, 6H), 4.40 (t, 2H), 1.36 (t, 6H), 6.45 (dd, 1H), 4.15 (t, 1H), 3.95 (d, 1H).
[0341] Nuclear magnetic resonance hydrogen spectrum of monomer B6: 1H NMR (300 MHz, DMSO, δ ppm): 5.61 (dd, 1H), 4.63 (dd, 1H), 4.38 (dd, 1H), 6.31 (m, 1H), 6.12 (dd, 1H), 6.41 (s, 1H), 5.83 (d, 1H).
[0342] Preparation method of positive electrode sheet 6-1 and battery 6-1:
[0343] According to the data listed in Table 5, under the condition of dew point ≤-45°C, monomers A6, B6 and initiator AIBN are mixed into the prepared positive electrode slurry C3 and mixed evenly, coated on aluminum foil, the coating speed is controlled, in-situ polymerization is carried out at a certain temperature for a period of time, air drying is carried out, and roller pressing is carried out to obtain the positive electrode sheet 6-1.
[0344] The negative electrode slurry F3 is coated on a copper foil, dried by air blast, and rolled to obtain a negative electrode sheet 6-1.
[0345] The positive electrode sheet 6-1, negative electrode sheet 6-1 and separator S4 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E6. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 6-1 containing battery materials.
[0346] Experimental Example 6-2
[0347] Preparation method of positive electrode sheet 6-2 and battery 6-2:
[0348] The preparation method of the positive electrode sheet 6-2 is substantially the same as the preparation method of the positive electrode sheet 6-1, except that the monomers A6 and B6 are replaced by the monomer A6, and the remaining steps are the same to obtain the positive electrode sheet 6-2;
[0349] The preparation method of battery 6-2 is substantially the same as that of battery 6-1, except that positive electrode sheet 6-1 is replaced by positive electrode sheet 6-2, and the remaining steps are the same to obtain battery 6-2.
[0350] Comparative Example 6-3
[0351] Preparation method of positive electrode sheet 6-3 and battery 6-3:
[0352] The preparation method of the positive electrode sheet 6-3 is substantially the same as the preparation method of the positive electrode sheet 6-1, except that the monomers A6 and B6 are replaced by the monomer B6, and the remaining steps are the same to obtain the positive electrode sheet 6-3;
[0353] The preparation method of battery 6-3 is substantially the same as that of battery 6-1, except that positive electrode sheet 6-1 is replaced by positive electrode sheet 6-3, and the remaining steps are the same to obtain battery 6-3.
[0354] Comparative Example 6-4
[0355] Preparation method of positive electrode sheet 6-4 and battery 6-4:
[0356] Under the action of initiator AIBN, monomers A6 and B6 are in situ polymerized to obtain polymer material G6-4, and then polymer material G6-4 is mixed into positive electrode slurry C3 and mixed evenly. The remaining steps are the same as the preparation method of positive electrode sheet 6-1 to obtain positive electrode sheet 6-4.
[0357] The preparation method of battery 6-4 is substantially the same as that of battery 6-1. The positive electrode sheet 6-1 is replaced with the positive electrode sheet 6-4. The remaining steps are the same to obtain battery 6-4.
[0358] Experimental Example 7-1
[0359] Monomer A7: Monomer B7:
[0360] Preparation method of monomer A7: The preparation method of A7 is as shown in Example 1 Monomer B1, by (CAS: 3084-40-0) (CAS: 4474-60-6) was obtained by reaction.
[0361] Preparation method of monomer B7: The intermediate was obtained by fluorination Under nitrogen protection, 0.2 mmol of the intermediate was added to a 25 mL Schlenk tube. 2mL dry dichloromethane, 0.2mmol NBS, after adding, heat to 40℃ and stir to react for 8h, terminate the reaction, evaporate under reduced pressure, and obtain the intermediate by column chromatography
[0362] Add 0.2 mmol of intermediate into a 25 mL reaction tube 100 μL (3M) NaOH, stir at room temperature for 8 h, terminate the reaction, add 5 mL of dichloromethane and 5 mL of water, extract with 3×5 mL of dichloromethane, combine the organic phases, wash the organic phases with saturated NaCl, dry with anhydrous sodium sulfate, filter, distill under reduced pressure, and obtain the intermediate by column chromatography
[0363] Under nitrogen protection, 0.2 mmol of the intermediate was added to a 25 mL Schlenk tube. 2mL dichloromethane, cooled to 0℃, added 0.2mmol acryloyl chloride dropwise, reacted for 1h after addition, returned to room temperature for 1h, added 5mL water, extracted with 3×5mL dichloromethane, combined the organic phases, washed with saturated NaCl, dried over anhydrous sodium sulfate, filtered, distilled under reduced pressure, and column chromatography to obtain the intermediate
[0364] Under nitrogen protection, 0.2 mmol of intermediate 5 and 2 mL of dry tetrahydrofuran were added to a 25 mL Schlenk tube, cooled to -78 °C, 0.2 mmol of n-butyl lithium (n-hexane solution) was added dropwise, and the reaction was continued for 30 min after the addition was completed. The mixture was returned to room temperature and distilled under reduced pressure to obtain monomer B7.
[0365] Nuclear magnetic resonance hydrogen spectrum of monomer A7, 1H NMR (300 MHz, DMSO, δ ppm): 8.38 (s, 1H), 4.56 (d, 2H), 3.66 (d, 6H), 3.87 (s, 2H), 1.98 (s, 3H), 5.79 (s, 1H), 5.72 (s, 1H).
[0366] Nuclear magnetic resonance hydrogen spectrum of monomer B7: 1H NMR (300 MHz, DMSO, δ ppm): 6.10 (dd, 1H), 5.74 (d, 1H), 5.24 (d, 1H).
[0367] Preparation method of positive electrode sheet 7-1 and battery 7-1:
[0368] According to the data listed in Table 5, under the condition of dew point ≤-40°C, monomers A7, B7 and initiator BPO are mixed into the prepared positive electrode slurry C6 and mixed evenly, coated on aluminum foil, the coating speed is controlled, in-situ polymerization is carried out at a certain temperature, air drying is carried out, and roller pressing is carried out to obtain the positive electrode sheet 7-1.
[0369] Metal lithium F4 is used as the negative electrode plate to obtain the negative electrode plate 7-1.
[0370] The positive electrode sheet 7-1, negative electrode sheet 7-1 and separator S1 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E7. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 7-1 containing battery materials.
[0371] Experimental Example 7-2
[0372] Preparation method of positive electrode sheet 7-2 and battery 7-2:
[0373] The preparation method of the positive electrode sheet 7-2 is substantially the same as the preparation method of the positive electrode sheet 7-1, except that the monomers A7 and B7 are replaced by the monomer A7, and the remaining steps are the same to obtain the positive electrode sheet 7-2;
[0374] The preparation method of battery 7-2 is substantially the same as that of battery 7-1, except that positive electrode sheet 7-1 is replaced by positive electrode sheet 7-2, and the remaining steps are the same to obtain battery 7-2.
[0375] Experimental Example 8-1
[0376] Monomer A8: MS (ESI) m / z 284.08 (MH) +
[0377] Monomer B8: MS (ESI) m / z 327.04 (MH) +
[0378] Preparation method of monomer A8: The preparation method of A8 is as shown in Example 3. (CAS: 3095-95-2) and (CAS: 1074-61-9) was obtained by reaction;
[0379] Preparation method of monomer B8: The preparation method of B8 is similar to that of monomer B1 in Example 1. (CAS: 1433993-67-9) and (CAS: 30674-80-7) was obtained by reaction;
[0380] Preparation method of positive electrode sheet 8-1 and battery 8-1:
[0381] According to the data listed in Table 5, under the condition of dew point ≤-50°C, monomers A8, B8 and initiator BPO are mixed into the prepared positive electrode slurry C5 and mixed evenly, coated on aluminum foil, the coating speed is controlled, in-situ polymerization is carried out at a certain temperature, air drying is carried out, and roller pressing is carried out to obtain the positive electrode sheet 8-1.
[0382] The negative electrode slurry F5 is coated on a copper foil, dried by air blast, and rolled to obtain a negative electrode sheet 8-1.
[0383] The positive electrode sheet 8-1, negative electrode sheet 8-1 and separator S1 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E8. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 8-1 containing battery materials.
[0384] Experimental Example 8-2
[0385] Preparation method of positive electrode sheet 8-2 and battery 8-2:
[0386] The preparation method of the positive electrode sheet 8-2 is substantially the same as the preparation method of the positive electrode sheet 8-1, except that the monomers A8 and B8 are replaced by the monomer A8, and the remaining steps are the same to obtain the positive electrode sheet 8-2;
[0387] The preparation method of battery 8-2 is substantially the same as that of battery 8-1, except that positive electrode sheet 8-1 is replaced by positive electrode sheet 8-2, and the remaining steps are the same to obtain battery 8-2.
[0388] Experimental Example 9-1
[0389] Monomer A9: Monomer B9:
[0390] Preparation method of monomer A9: A9 is an existing substance, CAS: 912629-06-2; MS (ESI) m / z 222.18 (MH) +; Preparation method of monomer B9: B9 is an existing substance, CAS: 2057465-70-8, MS (ESI) m / z 206.22 (MH) +.
[0391] Preparation method of positive electrode sheet 9-1, negative electrode sheet 9-1 and battery 9-1:
[0392] As shown in Table 5, under the condition of dew point ≤-60°C, monomers A9, B9 and initiator BPO are mixed into the prepared positive electrode slurry C4 and mixed evenly, and coated on aluminum foil, and the coating speed is controlled to be 0.5m / min to 75m / min, in-situ polymerized at a certain temperature, blown dried, and rolled to obtain a positive electrode sheet 9-1;
[0393] As shown in Table 5, monomers A9, B9 and initiator BPO were mixed into the prepared negative electrode slurry F2 and mixed evenly, and coated on copper foil at a coating speed of 0.5 m / min to 75 m / min, polymerized in situ, dried with air blast, and rolled to obtain a negative electrode sheet 9-1;
[0394] The positive electrode sheet 9-1, negative electrode sheet 9-1 and separator S2 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E9. The battery cell is left standing at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 9-1 containing battery materials.
[0395] Experimental Example 9-2
[0396] Preparation method of positive electrode sheet 9-2, negative electrode sheet 9-2 and battery 9-2:
[0397] The preparation method of the positive electrode sheet 9-2 is substantially the same as the preparation method of the positive electrode sheet 9-1, except that the monomers A9 and B9 are replaced by the monomer A9, and the remaining steps are the same to obtain the positive electrode sheet 9-2;
[0398] The preparation method of the negative electrode sheet 9-2 is substantially the same as the preparation method of the negative electrode sheet 9-1, except that the monomers A9 and B9 are replaced by the monomer A9, and the remaining steps are the same to obtain the negative electrode sheet 9-2;
[0399] The preparation method of battery 9-2 is roughly the same as that of battery 9-1, except that the positive electrode sheet 9-1 is replaced by the positive electrode sheet 9-2, and the negative electrode sheet 9-1 is replaced by the negative electrode sheet 9-2. The remaining steps are the same to obtain battery 9-2.
[0400] Comparative Example 9-3
[0401] Preparation method of positive electrode sheet 9-3, negative electrode sheet 9-3 and battery 9-3:
[0402] The preparation method of the positive electrode sheet 9-3 is substantially the same as the preparation method of the positive electrode sheet 9-1, except that the monomers A9 and B9 are replaced by the monomer B9, and the remaining steps are the same to obtain the positive electrode sheet 9-3;
[0403] The preparation method of the negative electrode sheet 9-3 is substantially the same as the preparation method of the negative electrode sheet 9-1, except that the monomers A9 and B9 are replaced by the monomer B9, and the remaining steps are the same to obtain the negative electrode sheet 9-3;
[0404] The preparation method of battery 9-2 is roughly the same as that of battery 9-1, except that the positive electrode sheet 9-1 is replaced by the positive electrode sheet 9-3, and the negative electrode sheet 9-1 is replaced by the negative electrode sheet 9-3. The remaining steps are the same to obtain battery 9-3.
[0405] Experimental Example 9-4
[0406] Preparation method of positive electrode sheet 9-4, negative electrode sheet 9-4 and battery 9-4:
[0407] The preparation method of the positive electrode sheet 9-4 is substantially the same as the preparation method of the positive electrode sheet 9-2, except that the monomer A9 and the initiator BPO are not added, and the remaining steps are the same to obtain the positive electrode sheet 9-4;
[0408] The preparation method of the negative electrode sheet 9-4 is exactly the same as the preparation method of the negative electrode sheet 9-2, and the negative electrode sheet 9-4 can be obtained;
[0409] The preparation method of battery 9-4 is roughly the same as that of battery 9-2, except that the positive electrode sheet 9-2 is replaced by the positive electrode sheet 9-4, and the negative electrode sheet 9-2 is replaced by the negative electrode sheet 9-4. The remaining steps are the same to obtain battery 9-4.
[0410] Experimental Example 9-5
[0411] Preparation method of positive electrode sheet 9-5, negative electrode sheet 9-5 and battery 9-5:
[0412] The preparation method of the positive electrode sheet 9-5 is exactly the same as the preparation method of the positive electrode sheet 9-2, and the positive electrode sheet 9-5 can be obtained;
[0413] The preparation method of the negative electrode sheet 9-5 is substantially the same as the preparation method of the negative electrode sheet 9-2, except that the monomer A9 and the initiator BPO are not added, and the remaining steps are the same to obtain the negative electrode sheet 9-5;
[0414] The preparation method of battery 9-5 is roughly the same as that of battery 9-2, except that the positive electrode sheet 9-2 is replaced by the positive electrode sheet 9-5, and the negative electrode sheet 9-2 is replaced by the negative electrode sheet 9-5. The remaining steps are the same to obtain battery 9-5.
[0415] Experimental Example 10-1
[0416] Monomer A10: MS (ESI) m / z 323.28 (MH)
[0417] Monomer B10:
[0418] Preparation method of monomer A10: The preparation method of A10 is as shown in Example 3. (CAS: 3095-95-2) and (CAS: 30674-80-7) was obtained by reaction;
[0419] Preparation method of monomer B10: (CAS: 247912-64-7) is obtained by hydrolysis under alkaline conditions.
[0420] Preparation method of positive electrode sheet 10-1, negative electrode sheet 10-1 and battery 10-1:
[0421] As shown in Table 5, under the condition of dew point ≤ -35°C, monomers A10, B10 and initiator AIBN are mixed into the prepared positive electrode slurry C1 and mixed evenly, coated on aluminum foil, coated, in-situ polymerized, blown dried, and rolled to obtain a positive electrode sheet 10-1.
[0422] As shown in Table 5, monomers A10, B10 and initiator AIBN were mixed into the prepared negative electrode slurry F1 and mixed evenly, and then coated on copper foil, coated, polymerized in situ, dried with air blast, and rolled to obtain a negative electrode sheet 10-1;
[0423] The positive electrode sheet 10-1, the negative electrode sheet 10-1 and the separator S1 containing the battery material are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then the electrolyte E1 is injected and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 10-1 containing battery materials.
[0424] Experimental Example 10-2
[0425] Preparation method of positive electrode sheet 10-2, negative electrode sheet 10-2 and battery 10-2:
[0426] The preparation method of the positive electrode sheet 10-2 is substantially the same as the preparation method of the positive electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer A10, and the remaining steps are the same to obtain the positive electrode sheet 10-2;
[0427] The preparation method of the negative electrode sheet 10-2 is substantially the same as the preparation method of the negative electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer A10, and the remaining steps are the same to obtain the negative electrode sheet 10-2;
[0428] The preparation method of battery 10-2 is substantially the same as that of battery 10-1, except that the positive electrode sheet 10-1 is replaced by the positive electrode sheet 10-2, and the negative electrode sheet 10-1 is replaced by the negative electrode sheet 10-2. The remaining steps are the same to obtain battery 10-2.
[0429] Experimental Example 11-1
[0430] Monomer A11: Monomer B11:
[0431] Preparation method of monomer A11: A11 is an existing substance, CAS: 2062619-95-6;
[0432] Preparation method of monomer B11: B11 is an existing substance, CAS: 1334816-35-1.
[0433] Preparation method of positive electrode sheet 11-1, negative electrode sheet 11-1 and battery 11-1:
[0434] According to the data listed in Table 5, under the condition of dew point ≤ -35°C, monomers A11, B11 and initiator BPO were mixed into the prepared positive electrode slurry C4 and mixed evenly, coated on aluminum foil, coated, in-situ polymerized, air-dried, and roll-pressed to obtain a positive electrode sheet 11-1;
[0435] As shown in Table 5, monomers A11, B11 and initiator BPO were mixed into the prepared negative electrode slurry F2 and mixed evenly, and then coated on copper foil, coated, polymerized in situ, dried with air blast, and rolled to obtain a negative electrode sheet 11-1;
[0436] The positive electrode sheet 11-1, negative electrode sheet 11-1 and separator S2 containing battery materials are stacked and baked to obtain a dry battery cell, and then the battery cell is placed in a packaging shell, and then injected with electrolyte E6. The battery cell is left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 11-1 containing battery materials.
[0437] Experimental Example 11-2
[0438] Preparation method of positive electrode sheet 11-2, negative electrode sheet 11-2 and battery 11-2:
[0439] The preparation method of the positive electrode sheet 11-2 is substantially the same as the preparation method of the positive electrode sheet 11-1, except that the monomers A11 and B11 are replaced by the monomer A11, and the remaining steps are the same to obtain the positive electrode sheet 11-2;
[0440] The preparation method of the negative electrode sheet 11-2 is substantially the same as the preparation method of the negative electrode sheet 11-1, except that the monomers A11 and B11 are replaced by the monomer A11, and the remaining steps are the same to obtain the negative electrode sheet 11-2;
[0441] The preparation method of battery 11-2 is substantially the same as that of battery 11-1, except that positive electrode sheet 11-1 is replaced by positive electrode sheet 11-2, and negative electrode sheet 11-1 is replaced by negative electrode sheet 11-2. The remaining steps are the same to obtain battery 11-2.
[0442] Experimental Example 12-1
[0443] Monomer A12: MS (ESI) m / z 300.03 (MH) +
[0444] Monomeric B12: MS (ESI) m / z 232.03 (MH) +
[0445] Preparation method of monomer A12: A12 is an existing substance, CAS: 85161-34-8;
[0446] Preparation method of monomer B12: B12 is an existing substance, CAS: 1009107-26-9.
[0447] Preparation method of positive electrode sheet 12-1, negative electrode sheet 12-1 and battery 12-1:
[0448] As shown in Table 5, under the condition of dew point ≤-35°C, monomers A12, B12 and initiator BPO are mixed into positive electrode slurry C1 and mixed evenly, coated on aluminum foil, the coating speed is controlled, in-situ polymerization is carried out at a certain temperature, air drying is carried out, and roller pressing is carried out to obtain positive electrode sheet 12-1.
[0449] As shown in Table 5, monomers A12, B12 and initiator BPO were mixed into the prepared negative electrode slurry F1 and mixed evenly, and then coated on copper foil, the coating speed was controlled, in-situ polymerization was performed, air drying was performed, and roller pressing was performed to obtain a negative electrode sheet 12-1;
[0450] The positive electrode sheet 12-1, negative electrode sheet 12-1 and separator S1 containing battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E1 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 12-1 containing battery materials.
[0451] Experimental Example 12-2
[0452] Preparation method of positive electrode sheet 12-2, negative electrode sheet 12-2 and battery 12-2:
[0453] The preparation method of the positive electrode sheet 12-2 is substantially the same as the preparation method of the positive electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer A12, and the remaining steps are the same to obtain the positive electrode sheet 12-2;
[0454] The preparation method of the negative electrode sheet 12-2 is substantially the same as the preparation method of the negative electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer A12, and the remaining steps are the same to obtain the negative electrode sheet 12-2;
[0455] The preparation method of battery 12-2 is substantially the same as that of battery 12-1, except that the positive electrode sheet 12-1 is replaced by the positive electrode sheet 12-2, and the negative electrode sheet 12-1 is replaced by the negative electrode sheet 12-2. The remaining steps are the same to obtain battery 12-2.
[0456] Table 5-1 Experimental example battery configuration
[0457]
[0458]
[0459]
[0460] Table 5-2 Preparation parameters of batteries in experimental examples and comparative examples
[0461]
[0462]
[0463] Battery Test
[0464] After the secondary battery was completely cured in situ, the first-week discharge capacity, first-week efficiency, and 400-cycle capacity retention rate of the battery were tested at room temperature. The test voltage range was 2.75 to 4.2 V, and the cycle mode was 0.5C / 1C (C represents the rate). The test results are shown in Table 6.
[0465] Table 6 Battery test results
[0466]
[0467]
[0468]
[0469] In Table 6, the capacity retention rates of battery 7-1, battery 7-2 and blank battery 5 are the capacity retention rates after 100 cycles, and the capacity retention rates of the remaining batteries are the capacity retention rates after 400 cycles.
[0470] The present application provides an electrode sheet, which is prepared by mixing a monomer containing a phosphorus-based structure with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the cycle stability and safety of the battery and prolongs the battery life.
[0471] It can be seen from Table 6 that in LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 In a solid-state battery system with lithium cobalt oxide as the positive electrode and graphite, silicon carbon, silicon oxygen carbon, and metallic lithium as the negative electrode, compared with the blank battery, the energy density of the solid-state battery prepared by the present invention is only slightly reduced, but the cycle stability performance of the battery is significantly improved.
[0472] The negative electrode sheet is prepared by mixing monomers A and B in the negative electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries (battery 1-1, battery 2-1, battery 3-1, battery 4-1) prepared from the negative electrode sheet have a battery capacity of 10.11 to 10.17 Ah and a capacity retention rate of 91.12% to 91.25% after 400 cycles. The solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 9-4) prepared by mixing monomer A in the negative electrode slurry and initiating in-situ polymerization of the monomers have a battery capacity of 9.89 to 9.98 Ah and a capacity retention rate of 90.34% to 90.51% after 400 cycles. The electrical properties of the corresponding blank batteries 1 to 3 are not much different (battery capacity is 9.81 to 9.92 Ah, and the capacity retention rate is 89.74% to 90.04% after 400 cycles). The electrical performance of the solid-state batteries (battery 1-1, battery 2-1, battery 3-1, battery 4-1) with in-situ polymerization of monomers A and B is better than that of the solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 9-4) with in-situ polymerization of monomers A and B. Figure 2 It can be seen intuitively that battery 1-1, battery 1-2 and battery 9-2 did not explode and the battery structure was intact, while battery 1-4, battery 1-11 and blank battery 1 all exploded severely and the batteries were seriously damaged, which further shows that the electrode sheet containing phosphorus-based polymer material prepared by adding monomers to electrode slurry and initiating in situ polymerization provided in the present application is applied to solid-state batteries, which can significantly improve the safety performance of the battery.
[0473] The positive electrode sheet was prepared by mixing monomers A and B into the positive electrode slurry and in-situ polymerization of the monomers was initiated. The solid-state batteries prepared from the positive electrode sheet (battery 5-1, battery 6-1, battery 7-1, battery 8-1) had a battery capacity of 10.16 to 10.31 Ah, a capacity retention rate of 91.13% to 91.28% after 400 cycles, and a capacity retention rate of 88.67% for battery 7-1 after 100 cycles. The solid-state batteries prepared by mixing monomer A in the positive electrode slurry and initiating in-situ polymerization of the monomers (battery 5-2, battery 6-2, battery 7-2, battery 8-2, battery 9-5) have a battery capacity of 9.92 to 10.21 Ah, a capacity retention rate of 90.43% to 90.52% after 400 cycles, and a capacity retention rate of 88.24% after 100 cycles of battery 7-2, which are lower than the electrical performance of the corresponding blank batteries 3 and 5 to 6 (battery capacity 9.81 to 9.98 Ah, a capacity retention rate of 89.74 to 89.81% after 400 cycles, and a capacity retention rate of 80.43% after 100 cycles of blank battery 5). This shows that the electrical performance of the solid-state batteries (battery 5-1, battery 6-1, batteries 7 to 8) with in-situ polymerization of monomers A and B is better than that of the solid-state batteries (battery 5-2, battery 6-2, battery 9-5) with in-situ polymerization of monomer A alone.
[0474] Battery 9-1, Battery 10-1, Battery 11-1, Battery 12-1 are prepared by simultaneously mixing monomer A and monomer B in positive and negative electrode slurry and polymerizing in situ, and their battery capacity is 10.11Ah to 10.24Ah, and the capacity retention rate after 400 cycles is 91.52% to 91.61%. The solid-state batteries (Battery 9-2, Battery 10-2, Battery 11-2, Battery 12-2) prepared by only simultaneously mixing monomer A in positive and negative electrode slurry and polymerizing in situ have a battery capacity of 10.02 to 10.07Ah and a capacity retention rate of 90.61% to 90.69% after 400 cycles, which are slightly higher than the corresponding blank battery 1 and blank battery 4, and lower than the solid-state batteries (Battery 9-1, Battery 10-1, Battery 11-1, Battery 12-1). It shows that the electrical performance of solid-state batteries with in-situ polymerization of monomers A and B (battery 9-1, battery 10-1, battery 11-1, battery 12-1) is better than that of solid-state batteries with in-situ polymerization of only monomer A (battery 9-2, battery 10-2, battery 11-2, battery 12-2).
[0475] From the above comparison, it can be seen that the electrode sheet is prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, battery 7-1, battery 8-1, battery 9-1, battery 10-1, battery 11-1, battery 12-1) prepared by the electrode sheet have a higher capacity retention rate after 400 cycles than the solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 7-2, battery 8-2, battery 9-2, battery 9-4, battery 9-5, battery 10-2, battery 11-2, battery 12-2) prepared by only mixing monomer A in the electrode slurry and initiating in-situ polymerization, indicating that the solid-state battery prepared by simultaneously mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers has higher cycle stability.
[0476] Battery 9-2 is prepared by mixing monomer A into both positive and negative electrode slurries. The battery capacity is 10.07Ah and the capacity retention rate after 400 cycles is 90.65%. Battery 9-4 and battery 9-5 are prepared by mixing monomer A only into the positive electrode slurry or the negative electrode slurry. Battery 9-2 is superior to batteries 9-4 and 9-5 in terms of electrical properties such as battery first-week efficiency, capacity, and cyclability (battery capacity is 9.95Ah~9.98Ah, and the capacity retention rate after 400 cycles is 90.32%~90.34%), indicating that the battery prepared by mixing monomers into both positive and negative electrode slurries is superior to the battery prepared only with positive electrode slurry or negative electrode slurry in its electrical properties, indicating that mixing in both positive and negative electrode slurries has higher cycle stability.
[0477] Battery 1-11 adds monomers to an electrolyte and injects them into a battery cell to initiate in-situ polymerization of the monomers; Battery 1-16 first prepares the monomers into a solid electrolyte by in-situ polymerization and then assembles a solid-state battery. Battery 1-11 (battery capacity 9.87Ah, capacity retention rate 89.36% after 400 cycles) and battery 1-16 (battery capacity 9.82Ah, capacity retention rate 89.19% after 400 cycles) have lower performance data in terms of first-week efficiency, capacity, cyclability and other electrical properties than battery 1-2 (battery capacity 9.94Ah, capacity retention rate 90.46% after 400 cycles), indicating that the in-situ polymerization after mixing in the electrode slurry in this application has certain advantages.
[0478] Battery 1-12 is prepared by coating a precursor solution containing monomer A on the surface of the negative electrode plate and then polymerizing it in situ, battery 1-13 is prepared by coating a precursor solution of monomer A on the surface of the diaphragm and then polymerizing it in situ, and battery 1-14 is prepared by coating a precursor solution of monomer A on the surface of the positive electrode plate and then polymerizing it in situ. In none of the above batteries are monomers polymerized in situ in the electrode slurry, and the electrical properties such as the first cycle efficiency, capacity, and cyclability of the battery (battery capacity 9.83Ah~9.87Ah, capacity retention rate 89.24%~89.37% after 400 cycles) are far less than battery 1-2 (prepared by mixing monomer A in the negative electrode slurry), which shows that only the order of mixing the monomer with the electrode slurry and then polymerizing in situ to generate the electrode plate and then generating the battery in this application will not reduce the electrical performance of the battery, but will improve the first efficiency, capacity retention rate, etc. to a certain extent.
[0479] Battery 1-15 is a battery that first polymerizes monomers in situ to prepare polymer materials and then mixes the polymer materials into the negative electrode slurry, which is different from the order of battery 1-2. However, the first-week efficiency, capacity, cyclability and other electrical performance data of battery 1-15 (battery capacity 9.81Ah, capacity retention rate 89.28% after 400 cycles) are lower than those of battery 1-2; battery 6-4 is first polymerized in situ and then mixed with the negative electrode slurry, and its electrical performance is far lower than that of battery 6-1; this shows that the order of preparing electrode sheets in the present application has certain advantages, and only by following the preparation method of electrode sheets in the present application can good results be obtained.
[0480] No initiator was added to battery 1-7 (battery capacity 9.72Ah, capacity retention rate of 89.17% after 400 cycles), monomers A and B could not polymerize, and the obtained battery 1-7 was almost the same as blank battery 1, and its electrical properties such as first-week efficiency, capacity, and cyclability were also not much different, and were much smaller than battery 1-1 in which monomers A and B were polymerized. In addition, battery 1-8 (battery capacity 9.69Ah, capacity retention rate of 87.83% after 400 cycles) did not have an initiator added, and monomer A could not polymerize, so its performance data was almost the same as that of blank battery 1, and was also much smaller than that of battery 1-2.
[0481] In batteries 1-5, 6-3 and 9-3, only monomer B is polymerized in situ, and the battery capacity is between 9.87 and 9.89 Ah, and the capacity retention rate after 400 cycles is 90.01% to 90.08%, which is far less than the electrical performance of battery 1-1.
[0482] K1 in battery 1-6 represents the acrylate of the prior art. The solid-state battery 1-6 is prepared by mixing monomers A and K1 in the electrode slurry and initiating in-situ polymerization to prepare the electrode sheet. The battery capacity is 9.89Ah and the capacity retention rate after 400 cycles is 89.89%, which is much smaller than the solid-state battery prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization. The performance data is not much different from that of battery 1-2, indicating that the monomer A+B in the present invention has higher cycle stability than A and acrylate.
[0483] The solid-state batteries (battery 1-3, battery 1-4) prepared using only monomer D have a battery capacity between 9.64Ah and 9.68Ah, and a capacity retention rate of 88.23% to 88.40% after 400 cycles; the solid-state batteries (battery 1-9, battery 1-10) prepared using monomers K2 and K3 have a battery capacity between 9.76Ah and 9.79Ah, and a capacity retention rate of 88.94% to 89.11% after 400 cycles.
[0484] Among them, monomers D1 and D2 do not contain phosphorus groups, while monomers A used in batteries in other experimental examples all contain phosphorus groups. Comparing the electrochemical performance of the above batteries in terms of first effect, capacity retention rate, etc., it can be seen that the battery has better electrochemical performance when it contains phosphorus groups. K2 used in battery 1-9 is to first prepare a gel polymer electrolyte and then assemble a solid-state battery. Battery 1-10 is to add K3 to the electrolyte and in situ polymerize it in the injected battery cell, but the effect data are all lower than that of battery 1-2 of the present application, indicating that only by mixing monomers and initiators with electrode active materials to generate electrode slurry, coating, and in situ polymerization can better electrical performance be achieved.
[0485] The monomer used in battery 1-17 is trimethyl phosphate, a common flame retardant in the prior art, but trimethyl phosphate is added to the electrolyte. Its performance in terms of first efficiency and capacity retention rate is lower than that of battery 1-1 and battery 1-2, which further shows that the present invention enables the electrode to have good capacity performance and cycle stability. This is mainly because the present invention adopts an in-situ mixing method in the electrode slurry, so that the surface of the electrode active material particles is coated with a thin layer of phosphorus-containing polymer material. The polymer layer can maintain a low interfacial impedance during the battery cycle, while homogenizing the ion flow, thereby ensuring the electrochemical performance of the battery.
[0486] The difference between monomers K5 and A1 used in battery 1-18 is that the P and double bond in K5 are pure carbon chains, while A1 contains ester groups. From the data of battery capacity and capacity retention rate after 400 cycles, it can be seen that monomers containing ester groups can obtain better electrical properties.
[0487] It can be seen from battery 1-19, battery 1-2 and battery 1-20 that if the content of phosphorus-based polymer material is too high, the battery's electrical properties such as energy density and cycle performance will be significantly reduced.
[0488] Battery safety performance test
[0489] The batteries prepared in the above experimental examples, the batteries prepared in the comparative examples and blank batteries 1-5 were subjected to acupuncture safety tests according to safety requirements and test methods for power batteries for electric vehicles in GB-T31485-2015 for lithium-ion batteries.
[0490] 1. Needle penetration test: The battery is charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; when the battery is fully charged (100% SOC), a φ8mm high-temperature resistant steel needle is used to penetrate the battery plate at a speed of 25mm / s from a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the punctured surface, and the steel needle stays in the battery; observe for 1h, monitor the change in the surface temperature of the battery cell during the process, and record whether the battery cell catches fire or explodes. The battery passes if it does not catch fire or explode. The results are shown in Table 7.
[0491] Table 7 Cell acupuncture result record
[0492]
[0493]
[0494] The present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the cycle stability and safety of the battery and prolongs the battery life.
[0495] As shown in Table 7, the electrode sheet is prepared by mixing monomers A and B in the negative electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries prepared from the electrode sheet (battery 1-1, battery 2-1, battery 3-1, battery 4-1) do not catch fire or explode during the puncture test. The surface temperature of the battery cell during puncture is 32.1-33.7°C, which is much lower than the surface temperature of blank batteries 1-3 (608.3-612.5°C), which significantly improves the battery safety. However, the solid-state batteries prepared by only mixing monomer A in the negative electrode slurry and initiating in-situ polymerization (battery 1-2, battery 2-2, battery 3-2, battery 4-1) do not catch fire or explode during the puncture test. The surface temperature of the battery cell during puncture is 32.1-33.7°C, which is much lower than the surface temperature of blank batteries 1-3 (608.3-612.5°C), which significantly improves the battery safety. The batteries did not catch fire or explode during the puncture test, and the surface temperature of the battery cells was 40.3-41.5°C during the puncture test, which was much lower than the surface temperature of the blank batteries, but higher than the surface temperature of the solid-state batteries in which monomers A and B were in situ polymerized (battery 1-1, battery 2-1, battery 3-1, battery 4-1), indicating that the safety of the solid-state batteries in which monomers A and B were in situ polymerized (battery 1-1, battery 2-1, battery 3-1, battery 4-1) was better than that of the solid-state batteries in which only monomer A was in situ polymerized (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 9-4).
[0496] The electrode sheet is prepared by mixing monomers A and B in the positive electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries prepared from the electrode sheet (battery 5-1, battery 6-1, battery 7-1, battery 8-1) do not catch fire or explode during the needle puncture test. The surface temperature of the battery cell during the needle puncture is 32.6-33.9°C, which is much lower than the surface temperature of blank battery 3, blank batteries 5 and 6 (602.2°C-620.4°C), which significantly improves the battery safety. The solid-state batteries prepared by only mixing monomer A in the positive electrode slurry and initiating in-situ polymerization (battery 5-2, battery 6-2, battery 7-2, battery 8-1) do not catch fire or explode during the needle puncture test. The surface temperature of the battery cell during the needle puncture is 32.6-33.9°C, which is much lower than the surface temperature of blank battery 3, blank batteries 5 and 6 (602.2°C-620.4°C), which significantly improves the battery safety. The batteries did not catch fire or explode during the puncture test, and the surface temperature of the battery cells was 40.5-41.1°C during the puncture test, which was also lower than the surface temperature of the blank batteries, but higher than the surface temperature of the solid-state batteries in which monomers A and B were in situ polymerized (battery 5-1, battery 6-1, battery 7-1, battery 8-1), indicating that the safety of the solid-state batteries in which monomers A and B were in situ polymerized (battery 5-1, battery 6-1, battery 7-1, battery 8-1) was better than that of the solid-state batteries in which only monomer A was in situ polymerized (battery 5-2, battery 6-2, battery 7-2, battery 8-2, battery 9-5).
[0497] Battery 9-1, Battery 10-1, Battery 11-1, Battery 12-1 are prepared by simultaneously mixing monomer A and monomer B in the positive and negative electrode slurries and polymerizing them in situ. The batteries do not catch fire or explode during the needle puncture test. The surface temperature of the battery cell during the needle puncture is 28.49-29.8°C, which is much lower than the surface temperature of blank batteries 1 and 4, significantly improving the battery safety; while the solid-state batteries (Battery 9-2, Battery 10-2, Battery 11-2, Battery 12-2) prepared by simultaneously mixing monomer A in the positive and negative electrode slurries and polymerizing them in situ, the batteries do not catch fire or explode during the needle puncture test During acupuncture, the surface temperature of the battery cell was 36.2-36.9°C, which is also much lower than the surface temperature of the blank battery, but higher than the surface temperature of the solid-state batteries with in-situ polymerization of monomers A and B (battery 9-1, battery 10-1, battery 11-1, battery 12-1). This shows that the safety of the solid-state batteries with in-situ polymerization of monomers A and B (battery 9-1, battery 10-1, battery 11-1, battery 12-1) is better than that of the solid-state batteries with in-situ polymerization of only monomer A (battery 9-2, battery 10-2, battery 11-2, battery 12-2), and is better than the blank batteries 1-6 without monomer A mixed in.
[0498] From the above comparison, it can be seen that the electrode sheet is prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers. The needle-punctured surface temperature of the solid-state batteries (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, battery 7-1, battery 8-1, battery 9-1, battery 10-1, battery 11-1, battery 12-1) prepared from the electrode sheet is much lower than that of the solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 7-2, battery 8-2, battery 9-2, battery 9-4, battery 9-5, battery 10-2, battery 11-2, battery 12-2) prepared by only mixing monomer A in the electrode slurry and initiating in-situ polymerization, indicating that the solid-state battery prepared by simultaneously mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers has higher cycle stability.
[0499] Battery 9-2 is prepared by mixing monomer A into both positive and negative electrode slurries, while batteries 9-4 and 9-5 are prepared by mixing monomer A only into the positive electrode slurry or negative electrode slurry. The surface temperature of battery 9-2 is 36.5°C, which is much lower than that of batteries 9-4 and 9-5 (41.5~41.7°C), indicating that the battery prepared by mixing monomers into both positive and negative electrode slurries has better safety performance than the battery prepared only with positive electrode slurry or negative electrode slurry, indicating that mixing in both positive and negative electrode slurries has higher safety and can reduce the surface activity of positive and negative electrode particles at the same time.
[0500] Battery 1-11 is a battery in which monomer A is mixed in an electrolyte and injected into a battery cell to initiate in-situ polymerization of the monomer; first, the monomer is polymerized in situ to prepare a solid electrolyte, and then a solid-state battery is assembled. The surface temperature performance data of batteries 1-11 and 1-16 are much higher than those of battery 1-2, indicating that the in-situ polymerization after mixing in the electrode slurry can significantly reduce the temperature of the electrode sheet and has a protective effect.
[0501] Battery 1-12 is a battery in which monomer A is only coated on the surface of the negative electrode plate and then polymerized in situ, battery 1-13 is a battery in which monomer A is coated on the surface of the diaphragm and then polymerized in situ, and battery 1-14 is a battery in which monomer A is coated on the surface of the positive electrode plate and then polymerized in situ. In none of the above batteries are monomers polymerized in situ in the electrode slurry, and the battery safety is far less than that of battery 1-2 (prepared by mixing monomer A in the negative electrode slurry). It is shown that only the sequence of mixing monomers with electrode slurry and then polymerizing in situ to generate electrode sheets and then to generate batteries in this application can protect the battery, significantly reduce the surface temperature of the battery cell, suppress the temperature rise of the battery, and avoid the danger of fire and explosion of the battery.
[0502] Battery 1-15 first prepares the polymer material by in-situ polymerization of the monomer and then mixes the polymer material into the negative electrode slurry, which is different from the order of battery 1-2, but the surface temperature of battery 1-15 is 411.6°C, which is much higher than that of battery 1-2; it also first prepares the polymer material by in-situ polymerization of the monomer and then mixes the polymer material into the positive electrode slurry, and its surface temperature is much higher than that of battery 6-1; this shows that the order of preparing electrode sheets in the present application has certain advantages, and only by following the preparation method of electrode sheets in the present application can good results be obtained.
[0503] Although monomers A and B were mixed in the electrode slurry in Comparative Example 1-7, no initiator was added, so the monomers were not polymerized in situ. The battery caught fire and exploded during the needle puncture test, and the surface temperature of the battery cell was 488.2° C. In addition, since no initiator was added to battery 1-8, monomer A could not be polymerized. The battery caught fire and exploded during the needle puncture test, and the surface temperature of the battery cell was 492.3° C.
[0504] In batteries 1-5, 6-3 and 9-3, only monomer B underwent in-situ polymerization. The batteries caught fire and exploded when punctured. The surface temperature of the battery cell was 601.5-603.2°C when punctured, which was not much different from that of blank batteries and was much higher than that of the batteries in the experimental examples of this application.
[0505] K1 in battery 1-6 represents acrylate in the prior art. The solid-state battery 1-6 is prepared by mixing monomers A and K1 in the electrode slurry and initiating in-situ polymerization to prepare the electrode sheet. The surface temperature of the battery cell is 47.5°C during needle puncture, which is much higher than that of the solid-state battery (battery 1-1) prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization. This shows that the monomer A+B in the present invention has higher safety performance than A and acrylate.
[0506] The solid-state batteries (battery 1-3 and battery 1-4) prepared with only monomer D caught fire and exploded when punctured, and the surface temperature of the battery cell was 598.5-600.7°C during puncture. The solid-state batteries (battery 1-9 and battery 1-10) prepared with monomers K2 and K3 did not catch fire or explode when punctured, and the surface temperature of the battery cell was 407.6-487.2°C during puncture.
[0507] Among them, monomers D1 and D2 do not contain phosphorus groups, while monomer A used in the batteries in other experimental examples contains phosphorus groups. Comparing the electrochemical performance of the above batteries in terms of first effect, capacity retention rate, etc., it can be seen that the battery has better safety performance when it contains phosphorus groups. Battery 1-9 uses K2 to prepare a gel polymer electrolyte first, and then assemble a solid-state battery. Battery 1-10 adds K3 to the electrolyte and injects it into the battery cell for in-situ polymerization, but the effect data are lower than that of battery 1-2 of the present application, and none of them passed the puncture test, indicating that only by mixing monomers and initiators with electrode active materials to generate electrode slurry, coating, and in-situ polymerization can better safety performance be achieved.
[0508] The monomer used in battery 1-17 is trimethyl phosphate, a common electrolyte flame retardant in the prior art, but adding the same amount of flame retardant as the monomer of the present invention has no flame retardant effect at all, and the flame retardant cannot fundamentally suppress the temperature rise of the battery, further indicating that the solid-state battery prepared by in-situ blending of phosphorus-based monomers in the electrode slurry of the present invention can significantly improve the safety of the battery.
[0509] The difference between the monomers K5 and A1 used in battery 1-18 is that the P and double bond in K5 are pure carbon chains, while A1 contains ester groups. From the data of the surface temperature of the battery cell, it can be seen that the monomers containing ester groups can obtain better safety performance.
[0510] It can be seen from batteries 1-2, 1-19 and 1-20 that if the content of phosphorus-based polymer material is too little, it is difficult to coat a thin layer of polymer material containing phosphorus groups on the surface of the electrode active material particles, and the battery will catch fire or explode when punctured, and the improvement in battery safety is not obvious. If the content of phosphorus-based polymer material is too much, the battery will not catch fire or explode when punctured, and although the safety of the battery can be greatly improved, the battery's electrical properties such as energy density and cycle performance will be reduced.
[0511] It can be seen from battery 1-2 and battery 1-11 to battery 1-16, battery 2-1 and battery 2-3, battery 5-1 and battery 5-3, battery 5-2 and 5-4 that the solid-state batteries prepared by monomer A or A+B using the following methods all caught fire and exploded when punctured by acupuncture. These methods include: 1. directly adding monomers and initiators into electrolyte and then injecting them into the battery core to initiate in-situ polymerization of monomers to prepare solid-state batteries; 2. preparing monomers and initiators into precursor liquid and coating them on the positive electrode, negative electrode or diaphragm surface and then initiating in-situ polymerization of monomers; 3. first initiating monomer polymerization in vitro to prepare polymer materials, and then mixing them into electrode slurry; 4. initiating in-situ polymerization of monomers to prepare solid electrolytes and then assembling solid-state batteries. The present invention prepares an electrode sheet containing phosphorus-based polymer materials by mixing monomers into electrode slurry and initiating in-situ polymerization of monomers. The solid-state battery prepared by the electrode sheet does not catch fire or explode when punctured by acupuncture. The above phenomenon further shows that the electrode sheet containing phosphorus-based polymer materials in the present application has higher safety. This is because by mixing monomers into the electrode slurry and initiating monomer polymerization in situ, the monomers can coat the surface of the electrode particles with a thin layer of polymer, blocking the direct contact between the electronic conductor and the electrode particles, reducing the direct contact between the electrode particles and the electrolyte, and reducing the surface activity of the electrode particles, thereby improving battery safety.
[0512] 2. Other safety tests
[0513] Hot box test: The battery is placed in a test box at a fully charged state (100% SOC), and the temperature in the test box is raised at a rate of 5°C / min. When the temperature in the box reaches 150°C, it is kept constant for 1 hour, and then cooled to RT. During the whole process, the battery passes if there is no smoke, fire, or explosion.
[0514] Overcharge test: Charge the battery to 1.5 times the upper cut-off voltage. The battery passes the test if it does not catch fire or explode.
[0515] Extrusion test: After fully charging the battery, place it in two planes and squeeze it perpendicular to the plate direction at a rate of 2mm / s. Stop squeezing when the voltage reaches 0V or the battery deformation reaches 50%. The battery passes the test if it does not catch fire or explode during the squeezing process.
[0516] The test results are shown in Table 8.
[0517] Table 8 Battery safety results record
[0518]
[0519]
[0520] The application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer with an electrode slurry and coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the safety of the battery.
[0521] As shown in Table 8, the electrode sheets were prepared by mixing monomers A and B in the electrode slurry or monomer A and initiating in-situ polymerization of the monomers. All solid-state batteries prepared from the electrode sheets passed the hot box, overcharge, and extrusion tests. The solid-state batteries prepared by mixing monomer B in the electrode slurry to initiate in-situ polymerization, the batteries containing monomer A or containing both monomers A and B but not polymerized, and the solid-state batteries containing only D1 and D2 and the blank batteries all failed the hot box, overcharge, and extrusion tests. Moreover, if the content of the phosphorus-based polymer material is too little, the battery fails the safety test because it is difficult to coat a thin layer of phosphorus-containing polymer material on the surface of the electrode active material particles, indicating that the addition of too little does not significantly improve the battery safety. If the content of the phosphorus-based polymer material is too much, the battery can pass the safety test, but although the safety of the battery can be greatly improved, the electrical properties of the battery, such as the energy density and cycle performance, will be reduced. However, the battery did not pass the hot box, overcharge, and extrusion tests when monomer A or A+B was introduced into the solid-state battery in the following ways: first, the monomer and initiator were directly added to the electrolyte and then injected into the battery cell to initiate the in-situ polymerization of the monomer to prepare the solid-state battery; second, the monomer and initiator were prepared into a precursor solution and coated on the positive electrode, negative electrode or diaphragm surface to initiate the in-situ polymerization of the monomer; third, the monomer polymerization was initiated in vitro to prepare a polymer material, and then mixed into the electrode slurry; fourth, the monomer was initiated to polymerize in situ to prepare a solid electrolyte and then assemble the solid-state battery; further indicating that the present invention improves the safety of the battery. This is because by mixing the monomer in the electrode slurry and initiating the polymerization of the monomer in situ, the monomer can be coated with a thin layer of polymer on the surface of the electrode particles, blocking the direct contact between the electronic conductor and the electrode particles, reducing the direct contact between the electrode particles and the electrolyte, and reducing the surface activity of the electrode particles, thereby improving the battery safety.
[0522] In the puncture test, hot box test, overcharge test, and extrusion test, monomer A or monomer A and B are mixed in the electrode slurry and the monomers are polymerized in situ to prepare electrode sheets. The solid-state batteries prepared from the electrode sheets all passed the test, and the solid-state batteries prepared by polymerization of both monomers A and B have better safety and better electrochemical performance. However, the monomers introduced into the solid-state battery by other means did not pass the safety test, such as directly adding the monomers and initiators to the electrolyte and then injecting them into the battery cell to initiate the in-situ polymerization of the monomers, preparing the monomers and initiators into precursor solutions and coating them on the positive electrode, negative electrode or diaphragm surface and then initiating the in-situ polymerization of the monomers, first initiating the polymerization of the monomers in vitro to prepare a polymer material, then mixing it into the electrode slurry, initiating the in-situ polymerization of the monomers to prepare a solid electrolyte, and then assembling the solid-state battery; while the solid-state batteries and blank batteries in which monomer A or A+B is mixed into the electrode slurry but polymerization is not initiated, or monomer B is mixed into the electrode slurry and in-situ polymerization is initiated, or only D1 or D2 is mixed, all failed the safety test. Moreover, if the content of phosphorus-based polymer material is too little, the battery fails the safety test because it is difficult to coat a thin layer of phosphorus-containing polymer material on the surface of the electrode active material particles, indicating that too little addition does not significantly improve the safety of the battery; if the content of phosphorus-based polymer material is too much, the battery can pass the safety test, although it can greatly improve the safety of the battery, it will reduce the battery's energy density and cycle performance and other electrical properties. This shows that the electrode sheet containing phosphorus-based polymer material obtained by in-situ mixing of phosphorus-based monomers in this application can be used in batteries, which can significantly improve the safety performance of the battery.
[0523] It should be noted that the monomer A in this patent, or the mixture of monomer A and monomer B, can also be directly used in combination with commercial electrolytes, and excellent results can still be achieved, indicating that the monomers used to prepare the polymer material in this application have good compatibility with various electrolytes.
[0524] In summary, the solid-state battery prepared by the present invention can not only significantly improve the battery safety performance, but also extremely well maintain the electrochemical performance of the battery, and is suitable for large-scale promotion and application.
[0525] In the present invention, only some structures are selected as representatives in the experimental examples to illustrate the preparation method and effects of the present application, and other structures not listed have similar effects.
[0526] The monomers used in the experimental examples can all be purchased or prepared simply, and the preparation processes are all existing technologies, so they are not described in detail in the specification.
[0527] It should also be noted that the applicant has conducted a large number of tests on this series of structures. Sometimes, in order to better compare with the existing system, the same structure and system have been tested more than once. Therefore, there may be certain errors in different tests.
[0528] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
[0529] The preferred specific implementation modes and embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above implementation modes, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present application.
Claims
1. An electrode sheet, comprising a current collector and an electrode material covering the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, characterized in that: The electrode material also includes a phosphorus-based polymer material; The mass proportion of the phosphorus-based polymer material in the electrode material is 0.08-20%; During the mixing process of the electrode material, monomers and initiators are added to perform in-situ polymerization to form an electrode sheet containing the phosphorus-based polymer material; The monomers include monomer A; The monomer A is at least one of the compounds shown in formula I, Formula I; Among them, R is , R2 and R3 can be connected to -C=O or -O-; R1 and R3 are independently selected from any one of a chain of 1 to 15 atoms with no, with or without a substituent; R2 is selected from any one of a chain or ring of 3 to 18 atoms, which is free, substituted or unsubstituted; R4 and R 44 It is a chain saturated alkyl group which may be substituted.
2. The electrode sheet according to claim 1, characterized in that The weight proportions of the components in the electrode material are: 80-98 parts of electrode active material, 0.2-10 parts of conductive agent, 0.2-10 parts of binder, and 0.1-20 parts of monomer.
3. The electrode sheet according to claim 1, characterized in that: The monomers also include monomer B; The monomer B is selected from at least one of the compounds shown in formula II, Formula II; Wherein R7 is selected from , , , , , Any of the following: A1 and A2 represent that atoms in the ring / chain can be substituted by a substituent.
4. The electrode sheet according to claim 3, characterized in that: R6 includes at least one of an ester group, an amide group or a phenylamide group.
5. The electrode sheet according to claim 3, characterized in that: R6 contains at least one ester group or amide group.
6. The electrode sheet according to any one of claims 1 to 5, characterized in that: The substituents include at least one of H, a halogen atom, =O, =S, an alkyl group, a heteroalkyl group, an alkenyl group, a heteroalkenyl group, an alkynyl group, a heteroalkynyl group, a hydroxyl group, a carbonyl group, an aldehyde group, a haloformyl group, a carboxyl group, an ester group, a peroxy group, an amine group, a quaternary ammonium salt group, an imino group C=N, an imide C(=O)NC(=O), an azo group, a thioether group, a disulfide group, a cyano group, a sulfonic acid group, a sulfonyl group, an amide group, a nitro group, a pyridyl group, an acyloxy group, a phenyl group, a benzyl group, a benzyloxy group, a phenoxy group, an acetyl group, a benzoyl group, and a benzyloxycarbonyl group.
7. The electrode sheet according to claim 5, characterized in that: The molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
8. A method for preparing an electrode sheet according to any one of claims 1 to 7, characterized in that: The electrode sheet is a positive electrode sheet and / or a negative electrode sheet, and the preparation method comprises: (1) taking an electrode active material, a conductive agent, a binder, a monomer, and an initiator, and mixing them uniformly to prepare a uniformly mixed slurry; (2) coating the uniformly mixed slurry on a current collector and polymerizing the mixture in situ to obtain the electrode sheet; The temperature of in-situ polymerization is 45~130℃, and the time of in-situ polymerization is 0.1~60min; The electrode active material, conductive agent, binder, monomer parts by weight: electrode active material 80 to 98 parts, conductive agent 0.2 to 10 parts, binder 0.2 to 10 parts, monomer 0.1 to 20 parts; The mass fraction of the initiator in the mixed slurry is 0.001% to 2%; The coating speed is 0.5m / min~75m / min.
9. A battery, characterized in that: The invention comprises the electrode sheet according to any one of claims 1 to 7 or the electrode sheet obtained by the preparation method according to claim 8.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
CN104518236A
Preparation method of all-solid-state polymer electrolyte and secondary lithium battery containing electrolyte
CN107785609A